Computational Analysis of Peptide Binding on Dengue-Associated Host Proteins POLR2A and Elongin C: Network Pharmacology, Molecular Docking, and Dynamics Simulation Insights - S. Mohammed Zaidh; M. H. Mohamed Asrarullah; Kathiravan Muthukumaradoss; N. Parvin; N. Irfan; Mohan Maruga Raja Muthu Kumaradoss (Journal of Pharmaceutical Innovation, 2027)

Comparative genomic analysis of hypervirulent and classical Klebsiella pneumoniae isolates from respiratory samples: A computational assessment of virulence genes - Manoj Kumar Thirugnanasambantham; Srimathy Ramachandran; Suma Mohan S.; Diraviyam Thirumalai (Functional & Integrative Genomics, 2026)

Multi-target molecular mechanisms of Cymbopogon flexuosus essential oil reveal membrane destabilization, ROS-mediated cellular damage, efflux perturbation, biofilm suppression and resistance-target interference in Staphylococcus aureus - Md Waquar Imam; Narendra Mohan; Nidhi Maurya; Chandan S. Chanotiya; Sudeep Tandon; Suaib Luqman (Archives of Microbiology, 2026)

MicroRNAs in dilated cardiomyopathy: from biomarkers to therapeutic targets - Abisha Vince Jeo V S; P. S. Sneha Sandra; Mahesh Mundalil Vasu; Jeemon Panniyammakal; Sanjay Ganapathi; Madhusoodanan Urulangodi; Neethu Mohan; P. R. Anil Kumar; Srikant Ambatipudi; Jyothi Vijay; Sivadasanpillai Harikrishnan (Molecular Biology Reports, 2026)

Wastewater antibody signatures reflect SARS-CoV-2 infection and immunization patterns in the population - Dhammika Leshan Wannigama; Mohan Amarasiri; Phatthranit Phattharapornjaroen; Cameron Hurst; Charin Modchang; John Giles; Jillian Gauld; Tanakorn Chantanasaro; Kazuhiko Miyanaga; Longzhu Cui; Stefan Fernandez; Hirotake Mori; et al. (Water Research, 2026)

Modular stacked bioelectrocatalytic-triphasic constructed wetland for continuous wastewater treatment - Vaibhav Nailwal; Boda Ravi Kiran; Triya Mukherjee; Pranavika Shinde; S. Sreelatha; S. Venkata Mohan (Bioresource Technology, 2026)

An analysis of the flow pattern of EICC during the positive Indian Ocean dipole events - Vishwanath Boopathi; Vidya S. Mohan; M. Jishad; Jaya Kumar Seelam (Regional Studies in Marine Science, 2026)

Non-stationary copula-based meteorological drought frequency analysis in response to climate change - Meera G. Mohan; S. Adarsh (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Tunable rGO–ZnO/CuO nanocomposites for energy storage applications: Enhanced electrochemical, antibacterial and thermal performance - Shibi Krishnan; Pillai Aswathy Mohan; Arun S. Prasad (Next Research, 2026)

Normalization of candidate reference genes for precise qRT-PCR quantification in Maruca vitrata F. (Lepidoptera: Crambidae) under multiple biotic and abiotic stress regimes - C. R. Chandana; Sushila Nadagouda; Muthugounder Mohan; A. Sunny Rao; Basavaraj S. Kalmath; Shivaleela Gouda; Jayaprakash M. Nidagundi; Saroja Narsinga Rao (International Journal of Tropical Insect Science, 2026)

Mimosa pudica Linn. - An important medicinal plant: Pharmacognostic evaluation, bioactive compound isolation, structural elucidation, and in silico analysis - Kousik Ghosh; Karthick Gopal; Lakshmanan Narayanan; Vamsee Krishna K․; Akansha Pandey; Aswathi Mohan P․; Siva Surya; Suseem S R; S. Chitra; Preeti Sharma; Ajay Kumar Meena (Next Research, 2026)

Preliminary Investigation of Phosphorus-Use Efficiency in Mungbean (Vigna radiata): A Comparative RNA-Seq Study - Deepali Kothari; Muraleedhar S. Aski; S. Premakumar; Bidwan Rath; Nirmala Pargaien; Lalit Mohan Tewari; Shouvik Das; Gyan Prakash Mishra; Gyanendra Singh; Prachi Shripatrao Yadav; Ya-Ping Lin; Roland Schafleitner; et al. (Indian Journal of Genetics and Plant Breeding, 2026)

Spatial distribution of metals in soils of an ecologically sensitive forest region of the Western Ghats, South India: vertical profiles, enrichment status, and health risk assessment - A. Sudha; C. S. Ratheesh Kumar; Roshni Mohan; P. V. Vidya; U. Sreejisha (Environmental Monitoring and Assessment, 2026)

Molecular and functional analysis of RNAi machinery genes in a neuropteran insect predator, Chrysoperla zastrowi sillemi - V. S. Chinnu; M. Mohan; R. Manjunatha; P. J. Aneesha; Suresh R. Jambagi (BioControl, 2026)

Unravelling the potential of Vitex negundo leaf extract in LPS-induced acute lung injury in mice through modulation of the TLR-4/NF-κB p65/iNOS pathway: Insights from integrated phytochemical characterization, in silico, and in vivo analysis - Mamta Meena; Meemansha Sharma; Ilavarasan S; Anand Mohan Mishra; Anshuk Sharma; Aneesha V.A.; Madhu Cholenahalli Lingaraju; Subhashree Parida; Vidya Singh; Vikash Chandra; Mausam Singh; Karuna Shanker; et al. (Tissue and Cell, 2026)

Direct reduction of low-grade taconite ore by atmospheric-pressure, microwave-powered hydrogen plasma - Vivek Pachchigar; Prashant Kumar Barnwal; Tanishka Kucheria; Daniel S. Ellis; Ivan Shchelkanov; Robert Stubbers; Brett Spigarelli; Brian Jurczyk; Jessica A. Krogstad; R. Mohan Sankaran (Minerals Engineering, 2026)

Integrated enzyme-assisted hot water biorefinery for enhanced recovery of bioactive compounds from brown seaweeds - C. S. Tejpal; S. M. Vijayakumar; K. M. Pradeep; Rahman K. Habbeb; T. G. Sumithra; C. O. Mohan; T. K. Anupama; R. Anandan (Journal of Applied Phycology, 2026)

DUST: A framework for quantifying dugong-seagrass interactions using low-cost UAVs - Midhun Mohan; Pandi P. Selvam; Milica Stankovic; Peter I. Macreadie; Daniel Gorman; Daria Agnieszka Karpowicz; Ian Hendy; Michael S. Watt; Daniele Ventura; Eben North Broadbent; Dimitris Poursanidis; Varsha Varsha; et al. (Marine Environmental Research, 2026)

Sedimentary phosphorous fraction composition in Ashtamudi wetland: implications on nutrient mobility, bioavailability, trophic state, and pollution - Roshni Mohan; Ratheesh Kumar C. S.; Sudha A.; Sreejisha U (Environmental Monitoring and Assessment, 2026)

Implementing automated task scheduling framework for fog network using adaptive actor critic deep reinforcement learning with sparse attention through multi-objective constraints - Rayroth Shashank; Aswin Kumer S V; Selvaganapathi Sennan; Thankaraj A; Britto Raj S; E. Mohan (Swarm and Evolutionary Computation, 2026)

Packaging films prepared from hot acid vs ultrasound-assisted microwave extracted pectin: a comparative study - Chandra Mohan Chandrasekar; Michael A. Jackson; Karl E. Vermillion; Kervin O. Evans; Andre K. White; Stefanie Simon; Arland T. Hotchkiss; Pankaj Koirala; Rishabh Goyal; Shyam S. Sablani; Wei Zhao (Food Hydrocolloids, 2026)

Influence of regional rainfall biases on sub-seasonal variability during boreal summer over South Asia in NGFS reanalysis - Bibhuti S. Keshav; Mohan T. S; Smrutishree Lenka; Nagarjuna Rao D; Raghavendra Ashrit; V.S. Prasad (Dynamics of Atmospheres and Oceans, 2026)

A deep learning prediction model for on-site earthquake early warning system in India - Bhargavi Podili; Pavan Mohan Neelamraju; Jahnabi Basu; S. T. G. Raghukanth (Journal of Seismology, 2026)

Influence of larval diet on the life table traits of Chrysoperla zastrowi sillemi using age-stage two-sex life table: insights for mass production - K. T. Shivakumara; T. Venkatesan; S. S. Udikeri; M. C. Keerthi; T. Sudha; M. Mohan; C. Manjunatha; G. S. Guruprasad (Journal of Plant Diseases and Protection, 2026)

Corrigendum to “Current status of mangrove conservation efforts in Qatar: A review”[Reg. Stud. Mar. Sci., vol. 79 (2024) 103822] - Pavithra S. Pitumpe Arachchige; Marcela Rondon; Abhilash Dutta Roy; Michael S. Watt; Mollie Davies; Dhouha Ouerfelli; Ewane Basil Ewane; Ammar Abulibdeh; Meshal Abdullah; Talal Al-Awadhi; Akshay Sharma; Ricardo Martínez Prentice; et al. (Regional Studies in Marine Science, 2026)

Derivation of seawater quality criteria for copper, cadmium, zinc, and mercury for the coastal and coral reef ecosystems of Gulf of Mannar, India - C M Ramakritinan; M Anand; L Palanikumar; Manoj Singh; S Manikandan; G Jayanthi; A K Kumaraguru; D Mohan; T Balasubramanian; B R Subramanian (Journal of Earth System Science, 2026)

A curcumin–resveratrol–carnosic acid complex mitigates brain–gut axis disruption in a rodent model of repeated mild traumatic brain injury - Mohind C Mohan; Anjana A S; Deepa Azhchath Vasu; Yadukrishnan M B; Aneesa P A; Tara Sudhadevi; Krishnakumar I M; Baby Chakrapani P S (Metabolic Brain Disease, 2026)

Investigating moist dynamics on sub-seasonal scales in the IMDAA reanalysis - Mohan T. S.; Smrutishree Lenka; Indira Rani; Niranjan Kumar Kondapalli; Nagarjuna Rao D; Saji Mohandas (Science of The Total Environment, 2026)

Unlocking the potential of wild edible fruits in the Garhwal Himalaya, India: Nutritional composition and future prospects - Yashwant Singh Rana; Om Prakash Tiwari; Chandra Mohan Sharma; Vikram S. Negi (Next Research, 2026)

Role of equatorial waves in modulating extreme temperature events over Sri Lanka - Bibhuti Sharan Keshav; Mohan T. S.; Raghavendra Ashrit (Theoretical and Applied Climatology, 2026)

Growth and wood anatomical properties of Acacia auriculiformis A.Cunn. ex Benth. planted under varied climatic conditions in Karnataka - Supriya K. Salimath; Ramakrishna Hegde; G. Ganapati; V. Maheswarappa; T. S. Hareesh; Mohan Varghese (European Journal of Forest Research, 2026)

Decadal variability and forcing mechanisms of the tropical Indian Ocean wind-driven circulation - G. Srinivas; Chhavi Goyal; Soumya Mohan; S. G. Aparna; Jasti S. Chowdary (Climate Dynamics, 2026)

Case study on Ustilaginoidea virens, the causal agent of rice false smut in India - Somshetty Ravali; S. Ameer Basha; SNCVL. Pushpavalli; Ahil Sajeli Begum; T. Kiran Babu; Y. Chandra Mohan; Banoth Balaji Naik (Australasian Plant Pathology, 2026)

Characterization, genomic insights and anti-biofilm potential of phage vB_PaeM_PKMS3, a lytic Pbunavirus capable of infecting clinical Pseudomonas aeruginosa isolates - Nivedya Mohan; K. S. Sritha; Jiya Jose; Sumi J. Menachery; Chandini C. Mohan; Asna T. Isshack; Honey Gopinathan; Sayuj Koyyappurath; K. Abhitha; Yogesh Bharat Dalvi; Sarita G. Bhat (Antonie van Leeuwenhoek, 2026)

Initial results of the novel acoustic-based apparatus to measure cumulative rainfall and its intensity - Shijo Zacharia; K S Hosalikar; Mrutyunjay Mohapatra; Manish R Ranalkar; Anjith Anjan; U K Shende; K N Mohan (Journal of Earth System Science, 2026)

Source characterisation of the trace metal composition in coastal sediments from Andaman and Nicobar Islands - V. Sachithanandam; Kiran Kumar Reddy; S. Sai Elangovan; P.M. Mohan; B.S.K. Kumar; G. Deviram; N.V. Vinithkumar (Regional Studies in Marine Science, 2026)

Decoding the non-covalent interactions of berry polyphenols with β-lactoglobulin - Ting Mao; Maneesha S. Mohan (Food Hydrocolloids, 2026)

Optimization of process control criteria for reducing Salmonella and Escherichia coli O157:H7 population on biltong - Hannah E. LeClair; Krishnabrunda Duggirala; Gopinath Mummaleti; Anuj S. Purohit; Anand Mohan (Food and Bioproducts Processing, 2026)

Drought-induced modulations in stomatal traits and potential conductance index of citrus rootstock genotypes - Amrut Sanjay Morade; Radha Mohan Sharma; Anil Kumar Dubey; Lekshmy Sathee; Darshan Manikrao Kadam; Ashok Kumar Mahawer; Vijaysinha D. Kakade; Sangram B. Chavan; S. Gurumurthy (Plant Physiology Reports, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unveiling the Schottky interface engineering in metal tellurides for scalable hydrogen production - V. Bharathi Mohan; S. Jayachitra; M. Sathish (Chemical Engineering Journal, 2026)

Regulation of PHB and PHBV production via substrate-driven microenvironment modulation in adapted-culture systems and scale-up studies - Uppalanchi Spoorthi; Yamini Javvadi; Diwakar Solanki; S. Venkata Mohan (Chemical Engineering Journal, 2026)

Evaluation of CMIP6 multi-model ensemble for assessing the intensity and duration of Indian monsoon under future warming scenarios - Smrutishree Lenka; Krushna Chandra Gouda; Rani Devi; T. S. Mohan (Climate Dynamics, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Technology advancements in future waste biorefineries: Focus on low carbon fuels and renewable chemicals - J. Shanthi Sravan; Shivali Sahota; Omprakash Sarkar; M. Venkateswar Reddy; S. Venkata Mohan; Young-Cheol Chang (Fuel, 2026)

Multimodal cell death induced by indirubin-3′-oxime through inhibition of Akt/mTOR axis in lung cancer cells - Na Young Kim; Shalini V. Gowda; Kachigere B. Harsha; D.C. Vinay Kumar; Chakrabhavi Dhananjaya Mohan; C.S. Shivakumara; Kanchugarakoppal S. Rangappa; Kwang Seok Ahn (Chemico-Biological Interactions, 2026)

Isolation and whole-genome characterization of multidrug-resistant Acinetobacter baumannii from Indian retail meat: unveiling high-risk clones and zoonotic transmission threats via comparative genomics - Vanishree B.; Wilfred Ruban Savariraj; Mohan H. V.; Jaganatha Rao; Porteen Kannan; Anbazhagan Subbaiyan; Sureshkannan S.; Nidhi Sudhakaran P.; Nithya Quintoil M.; Sivachandiran R.; Sivaraman Gopalan Krishnan; Raghavendra G. Amachawadi (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Challenges and opportunities integrating remote sensing for mangrove conservation in Papua New Guinea's complex natural and human landscapes - Midhun Mohan; Ewane Basil Ewane; Lara G. Moussa; Michael S. Watt; Peter I. Macreadie; Christopher J. Owers; Daria Agnieszka Karpowicz; Ian Reuben; Willie Doaemo (Regional Studies in Marine Science, 2025)

Late Holocene paleoceanography of the Knipovich Ridge area (Norwegian Sea) based on micropaleontological data - Tatiana S. Klyuvitkina; Ekaterina A. Novichkova; Elizaveta A. Agafonova; Lubov A. Lozinskaia; Karina S. Iakimova; Alexander G. Matul; Maria P. Chekhovskaya; Rahul Mohan; Anne de Vernal (Marine Micropaleontology, 2025)

Heteroleptic N, N donor carbonitrile based Au(III) complexes: DNA/BSA interaction studies, Molecular Docking, and cytotoxicity studies - Nikita J. Patel; Ravi A. Dabhi; Milan P. Dhaduk; Nirbhay K. Savaliya; Bhupesh S. Bhatt; Miral V. Lunagariya; Vaibhav D. Bhatt; Mohan N. Patel (Journal of Trace Elements in Medicine and Biology, 2025)

LIDAR based site assessment for rendezvous, docking and landing applications of autonomous space vehicle - Krishna Mohan; Sreeja S; Ponmalar M (Journal of Space Safety Engineering, 2025)

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Recurring eddies in the Southern Subtropical and Subantarctic Frontal regions of the Indian sector of the Southern Ocean during austral summer - P. Sabu; S. Cxynna; N.N.S. Vishnu; Nirmala J. Nair; Jenson V. George; N. Anilkumar; Rahul Mohan (Dynamics of Atmospheres and Oceans, 2025)

Biogas upgrading via hydrogenotrophic methanogenesis and hematite-GAC assisted in-situ CO₂-to-CH₄ conversion - Vemula Smrithi; Shalini Singh; S. Venkata Mohan (Chemical Engineering Journal, 2025)

Arsenic in Aquatic Ecosystems: Sources, Risks, Remediation, and Governance in India with Respect to Global Significance - Shailendra Mohan Raut; Kamal Sarma; Dilip H. Lataye; Saurav Kumar; Suryakant Bajirao Tarate; Vikash K. Sonu; Upendra R. Darla; S. P. Shukla; Indu Shekhar Singh; Ramesh Kumar Sahni; Sudhanshu Kumar; Pushpah Kumari Sharma; et al. (Water, Air, & Soil Pollution, 2025)

Mechanisms of tropical Indian Ocean circulation biases in CESM historical experiments - Mohan Soumya; Srinivas G.; S. Amritha (Theoretical and Applied Climatology, 2025)

Marine Debris Assessment Post-Hurricane Using Remote Sensing and Machine Learning Techniques - S. Venkatraman; V. Mohan; Eatedal Alabdulkreem; Achraf Ben Miled; Khalid Nazim Abdul Sattar; Setu Garg (Ocean Science Journal, 2025)

Reclaiming Saline Soils with Rice Husk Biochar as a Soil Amendment: Enhancing Soil Health and Promoting Okra Growth - Brahmacharimayum Preetiva; Abhishek Kumar Chaubey; Jonathan S. Singsit; Tej Pratap; Charles U. Pittman; Dinesh Mohan (Journal of Soil Science and Plant Nutrition, 2025)

Innovative augmentation techniques and optimized ANN model for imagined speech decoding in EEG-based BCI - Anand Mohan; R. S. Anand (Cognitive Neurodynamics, 2025)

Mitigating biofouling in cooling water system: Actibromide ® to combat Perna viridis infestation and environmental impact - Bandita Badakumar; D. Inbakandan; S. Venkatnarayanan; T. V. Krishna Mohan; Y. V. Nancharaiah; P. Veeramani; N. K. Pandey; P. Sriyutha Murthy (Biofouling, 2025)

UAV-supported mangrove restoration: nature-based solutions for controlling vector-borne disease incidence - Midhun Mohan; Shalini A. L. King; Lara G. Moussa; Michael S. Watt; Emma M. Awuku-Sowah; Gregory F. Albery; James Kairo; A. Aldrie Amir; Julius Sila; Peter I. Macreadie (Environmental Monitoring and Assessment, 2025)

Anticancer potential of phytocompound isolated from Asystasia gangetica leaves: extraction optimization, characterization, and toxicity assessment - Jayalakshmi Ramasamy; Latha Subbiah; Akshath U. S.; Niladri Sekhar Chatterjee; Swarnalatha Kodidela; Chandra Mohan Mittameedi; Raja Ganesan; Pavan Kumar Dara; Celine Hilda Mary S.; Selvamani Palanisamy (Natural Product Research, 2025)

Origin of leucosomes in a Kyanite-Zone migmatite of the Higher Himalayan Crystallines, Bhagirathi Valley (NW Himalaya) - Aman Kushwaha; Sandeep Singh; Shashank Prabha-Mohan; Ian S. Williams; Benita Putlitz; Lukas P. Baumgartner; Jean-Luc Epard (Journal of Asian Earth Sciences, 2025)

Similar size distributions of casein micelles determined by cryo-electron microscopy and nanoparticle tracking analysis - Maneesha S. Mohan; Isabella Loughland; Jared K. Raynes; Federico M. Harte; Carl Holt (International Dairy Journal, 2025)

In silico estimation of density, vapor pressure, distillation curve, and octane numbers of gasoline fuels using machine learning - Balaji Mohan; Fatema Alsaleh; Abdullah S. AlRamadan; Saud Almbdal; Alya Al-Ammari; Zainab Saihati; Alexander Voice; Jihad Badra (Fuel, 2025)

Hybrid deep learning with a fusion model of weather and soil-based multi-crop recommendations for improving crop sustainability - Mohan M; S. Anandamurugan (Theoretical and Applied Climatology, 2025)

Analysis of Two Heavy Rainfall Episodes in May 2022 and June 2022 in Southern Parts of Assam, Northeast India - S. I. Laskar; H. Baisya; S. Das; A. Sandeep; M. Mohapatra; K. N. Mohan (Pure and Applied Geophysics, 2025)

Effects of polyphenols on gut microbiota and inflammatory markers in individuals with overweight or obesity: a systematic review and meta-analysis of randomized controlled trials - Ting Mao; Yizi Zhang; Rakesh Kaushik; Maneesha S. Mohan (Critical Reviews in Food Science and Nutrition, 2025)

Microplastic contamination in urban groundwater: Risk assessment, citizen perception and policy imperatives – a case study of Kozhikode City, Kerala State, India - S. Sruthy; A. Navaneeth; K.Ch.V Naga Kumar; K.C. Jesni; M.B. Binish; Mahesh Mohan; U. Surendran; P.S. Harikumar; Manoj P. Samuel (Science of The Total Environment, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Unravelling the antifungal property of a type I crustin from Scylla olivacea: Membrane disruption and ROS generation as modes of action - S. Neelima; M.V. Anju; K. Archana; V.V. Anooja; P.P. Athira; M.R. Revathy; Anjali S. Mohan; Dhanya Kesavan; Rosamma Philip (Fish & Shellfish Immunology, 2025)

Retraction notice to “Green waste immobilized Ag/Cu feather like Bi-matrix on garment dye decomposes and their bio-efficacy” [Environ. Res. 242 (2024) 117761] - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan perumal (Environmental Research, 2025)

Sustainable CO₂ valorization through pilot-scale electro fermentation: CODH-driven upregulation for carbon-negative chemical production - Athmakuri Tharak; S. Venkata Mohan (Chemical Engineering Journal, 2025)

Triazolyl-indolo-quinoxaline triggers differential cell death pathways in pancreatic cancer via ROS/p38 axis - Bada Yoon; Rajaghatta N. Suresh; C.S. Shivakumara; Kachigere B. Harsha; Chakrabhavi Dhananjaya Mohan; Gautam Sethi; Kanchugarakoppal S. Rangappa; Kwang Seok Ahn (Chemico-Biological Interactions, 2025)

Potential benefits of biodiversity corridors for fragmented mangrove ecosystems - Amare Gebrie; Midhun Mohan; Daria Agnieszka Karpowicz; Abhilash Dutta Roy; Varsha Varsha; Jenny Zambrano; Ewane Basil Ewane; Michael S. Watt; Peter I. Macreadie; Ashraf Jaffar; Kim Calders; Sanjana Dutt; et al. (Biological Conservation, 2025)

Evaluating the impact of aircraft observations on meteorological forecasts over the Indian subcontinent during southwest monsoon - Kumarjit Saha; S Indira Rani; S Desamsetti; Greeshma M Mohan (Journal of Earth System Science, 2025)

Seasonal dynamics of dissolved and particulate organic carbon in nearshore waters of the Andaman Islands - P. M. Mohan; R. Karuna Kumari; N. V. H. K. Chari; Sai Elangovan S.; J. Joyson Joe Jeevamani; Mamidala Harikrishna Prasad; Supriyo Chakraborty; V. Sachithanandam (Frontiers in Marine Science, 2025)
This study investigates the seasonal and spatial variability of hydrochemical parameters and organic carbon pools between the South Andaman Islands (SAI) and North Andaman Islands (NAI) under contrasting monsoonal regimes. Seawater temperature (26.1 – 33.5°C) was consistently higher in SAI due to reef-associated stratification, while NAI exhibited greater variability. Salinity (25.2 – 35.9) and pH were more stable in SAI, whereas NAI showed lower values and higher variability driven by freshwater inputs from the Bay of Bengal river systems. Turbidity and dissolved inorganic nutrients (DIN, DIP, DSi) were significantly higher in NAI, reflecting strong terrestrial and riverine influence. Dissolved organic carbon (DOC; 103 – 772 µM) and particulate organic carbon (POC; 22 – 168 µM) concentrations were consistently higher in NAI, particularly during the spring intermonsoon (SIM) and northeast monsoon (NEM), while SAI exhibited lower but more variable concentrations linked to reef metabolism. Seasonal drivers included freshwater and terrestrial inputs enhancing DOC during SIM and NEM, and monsoon-induced mixing reducing concentrations during the southwest monsoon (SWM). POC levels were enriched in NAI throughout, whereas SAI showed greater variability related to reef-derived particulate cycling. The POC: DOC ratio (0.04 – 0.83) highlighted contrasting biogeochemical regimes, with NAI dominated by particulate-rich terrestrial inputs and SAI characterized by variable phytoplankton- and reef-driven processes. These findings emphasize the role of monsoonal forcing in shaping carbon dynamics across the Andaman Islands and the contrasting influence of terrestrial inputs in NAI versus reef-associated processes in SAI, with implications for regional carbon cycling and ecosystem functioning.

Efficient underwater ecological monitoring with embedded AI: detecting Crown-of-Thorns Starfish via DCGAN and YOLOv6 - Mohan Jyothimurugan; S. Pavithra; J. Deepika Roselind (Frontiers in Marine Science, 2025)
Introduction Coral reefs are among the most vital and diverse ecosystems on the planet, providing habitats for marine life, supporting fisheries, and protecting coastlines. However, they are increasingly threatened by outbreaks of Crown-of-Thorns Starfish (COTS), a coral-eating predator capable of causing large-scale reef destruction. Traditional monitoring methods rely on manual diver surveys, which are time-consuming, labour-intensive, and unsuitable for rapid large-scale assessments. Methods To address these limitations, this study proposes an AI-powered framework for detecting COTS in underwater imagery. The system integrates advanced deep learning object detection techniques with synthetic data augmentation to improve model robustness and adaptability under complex underwater conditions. Synthetic training images were generated to expand dataset variability, while optimized detection models were designed for high accuracy and real-time inference. Results The final detection model demonstrated strong performance, achieving a precision of 0.927, recall of 0.903, and mAP@50 of 0.938. These results indicate the effectiveness of the framework in accurately identifying COTS across diverse underwater environments. Discussion and Conclusion The proposed solution is designed for deployment on embedded systems, ensuring practical, scalable, and efficient monitoring of coral reef ecosystems. By enabling real-time and high-accuracy detection of COTS, this framework supports timely interventions and contributes to the conservation and ecological resilience of coral reefs, particularly in vulnerable regions such as the Great Barrier Reef.

Pharmacognostical studies of the leaf and stem of Tetrastigma leucostaphylum (Dennst.) Alston ex Mabb. with special reference to soil chemistry - Stephy P. P.; Prasobh K. Mohan; Adarsh Krishna T.P.; Ajeesh Krishna T.P.; Selva Kumar S.; Walter Christhuraj C.; Soosai Raj S. (Vegetos, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Neurobehavioural assessment of hesperitine and epigallocatechin gallate in aluminium chloride-induced neurotoxicity in zebrafish model - A. Madeswaran; V. Keerthana; M. Shelpa; S. Kaladharan; B. Varunkumar; S. Mohan (Next Research, 2025)

Insecticide degradation potential of aphid associated bacteria - Mahesh S. Yandigeri; Sampada N.; Manoj Kumar Solanki; Sanjay Yalashetti; M. Mohan; G. Sivakumar; B.S. Manjunatha; S.N. Sushil (Biocatalysis and Agricultural Biotechnology, 2025)

Local Delivery of Non-opioid Analgesic Microparticles to Modulate Post-surgical Pain - Prerna Mohan; Jeladhara Sobhanan; Caitlyn M. Gaffney; Nitisha Mehrotra; Fernando J. Cabrera; Richard Lee; Aparna Adumbumkulath; Eric Haas; Andrew J. Shepherd; Crystal S. Shin; Ghanashyam Acharya (Pharmaceutical Research, 2025)

Evaluation of policy interventions to mitigate the prevalence of household air pollution due to biomass fuel and its associated health risks in rural India - Yaparla Deepthi; Amit Passi; Chithra V. S; Lekshmi Mohan V; Smaranika Panda; S. M. Shiva Nagendra (Air Quality, Atmosphere & Health, 2025)

Antimicrobial Peptide So-Crustin as a Therapeutic Agent against WSSV Infection in Penaeus monodon Culture System, Conferring Better Protection and Survival - S. Neelima; Anjali S. Mohan; Dhanya Kesavan; A. Muneer; Rosamma Philip (International Journal of Peptide Research and Therapeutics, 2025)

The macroeconomic impact of disasters: a review of hurricanes in Caribbean small island developing states - Preeya S. Mohan; Eric Strobl (Climate and Development, 2025)

Optimizing mangrove afforestation site selection in gulf cooperation council nations using remote sensing and machine learning - Abhilash Dutta Roy; Midhun Mohan; Ian Hendy; Reem AlMealla; Michael S. Watt; John A. Burt; Juan Pablo Torres-Florez; Amna Almansoori; Nessrine Alzahlawi; Meshal Abdullah; Tarig Ali; Manickam Nithyanandan; et al. (Science of The Total Environment, 2025)

Deciphering the Variations in the Generalized Extreme Value Distribution Parameters in the Non-stationary Flood Frequency Analysis - Meera G. Mohan; Adarsh S (Water Resources Management, 2025)

Validation and assessment of Potential Fishing Zone (PFZ) dynamics along the southwest coast of India through environmental proxies and trophic guild analysis - Dhanya Mohan Lal; Harisha; Alakes Samanta; Sudheer Joseph; S Suresh Kumar; Sanjiba Kumar Baliarsingh; T M Balakrishnan Nair (Environmental Impact Assessment Review, 2025)

Fabrication of CoTe-phosphorus doped g-C3N4 photocatalytic engine: A leap towards eco-friendly hydrogen production - V. Bharathi Mohan; S. Jayachitra; P. Devi; P. Murugan; M. Sathish (Chemical Engineering Journal, 2025)

Effects of soil and climatic variables on earthworm community structure at altitude in the Himalayan forest ecosystem - Shakoor Ahmed; Naseer Hussain; R. S. Pandiya Rajan; Jatinder Mohan Julka; Nithyanandam Marimuthu (Community Ecology, 2025)

A Comprehensive Review on Ethnic Fermented Millet Food Products and its Applications: A Global Scenario - Mulukuri Naveena; R. Jagan Mohan; N. Baskaran; S. Vignesh (Current Food Science and Technology Reports, 2025)

Advancing oyster habitat mapping: Integrating satellite remote sensing to assess coastal development impacts in northern United Arab Emirates - Pandi Selvam P; Midhun Mohan; Abhilash Dutta Roy; Tarig Ali; Michael S. Watt; Fatin Samara (Marine Pollution Bulletin, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Exploring non-covalent interactions of β-casein with six polyphenols - Ting Mao; Muhammed Shijas Vallikkadan; Maneesha S. Mohan (Food Research International, 2025)

Structural, quality, and shelf-life assessment of pasta enriched with seaweed Ulva lactuca - E. Harsha Mohan; S. Madhusudan; J.N. Shashanka Rao; P.R. Monika; P. Prabhasankar; Revathy Baskaran (Food Bioscience, 2025)

Impact of water availability on food security in GCC: Systematic literature review-based policy recommendations for a sustainable future - Lara G. Moussa; Midhun Mohan; Pavithra S. Pitumpe Arachchige; Hasara Rathnasekara; Meshal Abdullah; Ashraf Jaffar; Jorge F. Montenegro; Apoorwa Kale; Joe Heng; ShaliniA.L. King; Redeat Daneil; Talal Al-Awadhi; et al. (Environmental Development, 2025)

Comprehensive Analysis of Sugarcane Resistance to Borers: Biophysical and Biochemical Screening in Pantnagar Region of Uttarakhand - Saba Tanveer; Ravi Prakash Maurya; A. S. Jeena; Rajat Mohan Bhatt (Sugar Tech, 2025)

Mechanical Evaluation of Granular Sub-base Reinforced with Recycled Tyres: A Way Towards Sustainability - Mohan Badiger; K. H. Mamatha; S. V. Dinesh (Geotechnical and Geological Engineering, 2025)

Eco-friendly structures for sustainable mangrove restoration - Midhun Mohan; Pandi P. Selvam; Ewane Basil Ewane; Lara G. Moussa; Emma F. Asbridge; Stacey M. Trevathan-Tackett; Peter I. Macreadie; Michael S. Watt; Lucy Gwen Gillis; Francoise Cabada-Blanco; Ian Hendy; Eben North Broadbent; et al. (Science of The Total Environment, 2025)

Assessing repurposing options for abandoned mines and quarries in Victoria, Australia using spatial MCDA - Shushil Giri; Oliver S. Holt; Grace Tully; Alec Miller; Mohan Yellishetty; David Whittle; Peter M. Bach (Resources, Conservation and Recycling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Anaerobic conversion of de-oiled yeast biomass fractionation waste to biomethane and biohydrogen for resource efficiency in biorefineries - Ayan Banerjee; Shalini Singh; Thallada Bhaskar; S. Venkata Mohan; Debashish Ghosh (Journal of Environmental Management, 2025)

Contamination of groundwater by microorganisms and risk management: Conceptual model, existing data, and challenges - A.J. Natishah; Melvin S. Samuel; Karrun Velmurugan; S.R. Showparnickaa; S.M. Indumathi; Mohan Kumar (Groundwater for Sustainable Development, 2025)

Fidelity of coupled hindcast simulations in representing intraseasonal biases over South Asia - D. Nagarjuna Rao; T. S. Mohan; Ankur Gupta; Kondapalli Niranjan Kumar; Akhilesh Mishra; Imranali M. Momin; Saji Mohandas; Ashis K. Mitra; V. S. Prasad (Climate Dynamics, 2025)

Nitrogen ameliorates NaCl toxicity in eggplant seedlings: Role of hydrogen sulphide and sulphur metabolic signaling - Madhulika Singh; Pratibha Singh; S. Shweta; Utkarsha Singh; Sheo Mohan Prasad (Biocatalysis and Agricultural Biotechnology, 2025)

Alpha-bisabolol inhibits yeast to hyphal form transition and biofilm development in Candida albicans: in vitro and in silico studies - Sayali Chougule; Shivani Patil; Tanjila Gavandi; Sargun Basrani; Ashwini K. Jadhav; S. Mohan Karuppayil (In Silico Pharmacology, 2025)

Characterising cowpea (Vigna unguiculata L. Walp) mini-core set for flowering responses to various photoperiod and temperature regimes - T. Lakshmi Pathy; A. Mohan Rao; T. V. Krishna; Kuldeep Tripathi; S. Ramesh; N. Akshay Rahul; Akshata G. Bhat; Pratibha B. Honnannavar (Genetic Resources and Crop Evolution, 2025)

Assessment of sweetpotato germplasm for selection of day-neutral genotypes for tropical India - Shirly Raichal Anil; M. N. Sheela; C. Mohan; A. N. Jyothi; C. Visalakshi Chandra; S. Shanawas; J. Sreekumar (Euphytica, 2025)

Retraction notice to “Rationally construction of 2D & 3D material on h-BN @ SnO2/TiO2 micro-sphere enables for photocatalytic debasement of textile cloth dyes in waste water treatment” [Environ. Res. 251-P2 (2024) 118728] - A. Vasantham; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan Perumal (Environmental Research, 2025)

Retraction notice to “Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation” [Environ. Res. 242 (2024) 117625] - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2025)

Enhanced biomethane production from carbon dioxide, catalyzed by a single chamber bioelectrochemical system at elevated pressure - Sai Kishore Butti; S. Venkata Mohan (Chemical Engineering Journal, 2025)

Climate change adaptation in small island developing states: evidence from the nationally determined contributions of Caribbean States - Preeya S. Mohan (Regional Environmental Change, 2025)

Ground motion model for acceleration response spectra using conditional-generative adversarial network - Pavan Mohan Neelamraju; Jahnabi Basu; S. T. G. Raghukanth (Natural Hazards, 2025)

Cognizance about sea water intrusion by chemical analysis in coastal aquifer of southeast coast of India - V. Baskaran; M. Sridharan; R. Saravanane; S. Mohan (International Journal of Energy and Water Resources, 2025)

Classification of Imagined Speech Signals Using Functional Connectivity Graphs and Machine Learning Models - Anand Mohan; R. S. Anand (Brain Topography, 2025)

Mangrove-based carbon market projects: What stakeholders need to address during pre-feasibility assessment - Ewane Basil Ewane; Pandi P. Selvam; Reem AlMealla; Michael S. Watt; Pavithra S. Pitumpe Arachchige; Barbara Bomfim; Wan Shafrina Wan Mohd Jaafar; Soheil Salehian; Tarig Ali; Nithyanandan Manickam; Meshal M. Abdullah; Sophie Westover; et al. (Journal of Environmental Management, 2025)

Estimation of cetane number using machine learning - Balaji Mohan; Abdullah S. AlRamadan (Fuel, 2025)

Tandemly duplicated Rubisco activase genes of cereals show differential evolution and response to heat stress - Ragupathi Nagarajan; Kaviraj Singh Kahlon; Amita Mohan; Kulvinder S. Gill (Plant Molecular Biology, 2025)

Citrinin (CIT), a polyketide mycotoxin from a mangrove endophytic fungus Penicillium rubens EF 363 and its bioactive potential - M. R. Revathy; Anjali S. Mohan; Dhanya Kesavan; M. Dhaneesha; P. V. Santhini; Muralidharan Vanuopadath; Bipin G. Nair; Remington X. Poulin; T. P. Sajeevan; Rosamma Philip (Vegetos, 2025)

Advanced oxidation processes for coffee processing wastewater treatment: Current developments and future directions - Gayathri Mohan; Shishir Kumar Behera; S. Shanthakumar (Journal of Water Process Engineering, 2025)

International climate finance in land use, land use change and forestry in Caribbean Small Island Developing States - Preeya S. Mohan (Forest Policy and Economics, 2025)

Distribution and habitat suitability of the endangered lion-tailed macaque Macaca silenus and other primate species in the Kodagu region of the Western Ghats, India - T. S. Kavana; K. Mohan; Joseph J. Erinjery; Mewa Singh; Werner Kaumanns (Primates, 2025)

Predominance of non-covalent interactions of polyphenols with milk proteins and their health promoting properties - Ting Mao; Philip Wescombe; Maneesha S. Mohan (Critical Reviews in Food Science and Nutrition, 2024)

Edible packaging systems for improved microbial quality of animal-derived foods and the role of emerging technologies - Zuhaib F. Bhat; Hina F. Bhat; Maneesha S. Mohan; Rana Muhammad Aadil; Abdo Hassoun; Abderrahmane Aït-Kaddour (Critical Reviews in Food Science and Nutrition, 2024)

Thermodynamics link with lightning incidents in Tamil Nadu, India - S Kokilavani; V Geethalakshmi; S P Ramanathan; S D Pawar; V Gopalakrishnan; Somnath Mahapatra; Jayesh Chhagan Dhangar; Ga Dheebakaran; N K Sathyamoorthy; M Selva Kumar; S Mohan Kumar; Manoj A Domkawale (Journal of Earth System Science, 2024)

Rice night-time thirst: Genotype nutrient needs reflected in nocturnal transpiration - Spoorthi Nagaraju; Mohan Ramesh; Noor E Mujjassim; Sandeep Reddy A S; Preethi Vijayaraghavareddy; Sheshshayee Sreeman (Rhizosphere, 2024)

Current status of mangrove conservation efforts in Qatar: A review - Pavithra S. Pitumpe Arachchige; Marcela Rondon; Abhilash Dutta Roy; Michael S. Watt; Mollie Davies; Dhouha Ouerfelli; Ewane Basil Ewane; Ammar Abulibdeh; Meshal Abdullah; Talal Al-Awadhi; Akshay Sharma; Ricardo Martínez Prentice; et al. (Regional Studies in Marine Science, 2024)

Chromoionophores decorated silica-polymer hybrid monolith as the solid-state optical sensor for the simultaneous detection of Pb2+, Hg2+, and Cd2+ in aqueous and cigarette samples - Sangeetha Krishna Kumar; Prabhakaran Deivasigamani; Satheesh Kuppusamy; Pitchaiah K Chinaraga; C V S Brahmmananda Rao; Sivaraman Nagarajan; Akhila Maheswari Mohan (Journal of Environmental Chemical Engineering, 2024)

Milk adulteration: From detection to health impact - Ganesh B. Patil; Sakshi P. Wani; Piyush S. Bafna; Vishal S. Bagul; Mohan G. Kalaskar; Rakesh E. Mutha (Food and Humanity, 2024)

High temperature stress induced changes in physiological, biochemical, hormonal and gene expression patterns in contrasting tomato genotypes - Vijayakumar Amrutha; Mohan Reshma; R. V. Manju; K. N. Anith; Pratheesh P. Gopinath; S. Sarada; R. Beena (Plant Physiology Reports, 2024)

Chrysin downregulates the expression of ADAMTS-4 in foam cells - S. S. Aswani; Sreelekshmi G. Jayan; Mithra S. Mohan; N. S. Aparna; P. T. Boban; K. Saja (Molecular Biology Reports, 2024)

Physiological Responses to Acute Heat Stress in Rohu, Labeo rohita: Insights from Liver Proteomics - Mohan R. Badhe; Priyanka Das; Sonalina Sahoo; Anirban Paul; Pramoda Kumar Sahoo; R. Rajendra Kumar Reddy; Amol R. Suryawanshi; Priyanka C. Nandanpawar; Kanta Das Mahapatra; Naresh S. Nagpure; Mukunda Goswami; Jyotirmaya Mohanty (Marine Biotechnology, 2024)

Mangrove forest regeneration age map and drivers of restoration success in Gulf Cooperation Council countries from satellite imagery - Midhun Mohan; Abhilash Dutta Roy; Jorge F. Montenegro; Michael S. Watt; John A. Burt; Aurelie Shapiro; Dhouha Ouerfelli; Redeat Daniel; Sergio de-Miguel; Tarig Ali; Macarena Ortega Pardo; Mario Al Sayah; et al. (Remote Sensing Applications: Society and Environment, 2024)

Integrating S1A microwave remote sensing and DSSAT CROPGRO simulation model for groundnut area and yield estimation - Subramanian Thirumeninathan; Sellaperumal Pazhanivelan; Ramalingam Mohan; Anandan Pouchepparadjou; N.S. Sudarmanian; Kaliaperumal Ragunath; Lakshminarayanan Aruna; S. Satheesh (European Journal of Agronomy, 2024)

Performance evaluation of bio-concrete: An analysis of biomineralization capabilities, microstructural and mechanical properties - Priya S. Nair; Rajesh Gupta; Vinay Agrawal; Niha Mohan K; Blessen Skariah Thomas; Shanone C. Pereira; Abhishek Jain (Sustainable Chemistry and Pharmacy, 2024)

Chromoionophoric molecular probe infused bimodal porous polymer rostrum as solid-state ocular sensor for the selective and expeditious optical sensing of ultra-trace toxic mercury ions - Prabhakaran Srinivasan; Sushmitha P Sivaraman; Akhila Maheswari Mohan; Deepan Kumar Madhu; Pitchaiah K Chinaraga; C V S Brahmananda Rao; Sivaraman Nagarajan; Prabhakaran Deivasigamani (Journal of Hazardous Materials, 2024)

Anaerobic Process Intensification via Electro-methanogenesis − Advancing Biogas Upgradation through CO2 Utilization - J. Shanthi Sravan; Shalini Singh; S. Venkata Mohan (Chemical Engineering Journal, 2024)

Essential oil composition and anti-inflammatory activity in wild citrus from northeast India - Aakash Maurya; Bhavya Priyadarshini Mishra; Ram Mohan; Vivek Kumar Sharma; Narayanan K. Nair; Alok Lehri; Tikam S. Rana (Biochemical Systematics and Ecology, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Shake-table testing of two adjacent similar building frames connected with optimal viscoelastic dampers - Ramakrishna Uppari; S. C. Mohan (Innovative Infrastructure Solutions, 2024)

Development of micro dust reinforced composite for building applications - S. Mohan; G. Thilagavathi; Rangam Rajkhowa (Journal of Cleaner Production, 2024)

Influence of synthetic carbon grade on the metabolic flux of polyhydroxyalkanoate monomeric constitution synthesized by Bacillus cereus AAR-1 - A.R. Akinwumi; O.C. Nwinyi; A.O. Ayeni; S. Venkata Mohan (Bioresource Technology Reports, 2024)

Nutrient dynamics and sustainability of short rotation Eucalyptus camaldulensis plantations in southern India - Roby Mathew; D. S. Guru Murthy; Mohan Varghese (New Forests, 2024)

Assessment of extreme rainfall events for iFLOWS Mumbai in NCUM regional forecasting system - Mohan S. T; Raghavendra Ashrit; Kondapalli Niranjan Kumar; Upal Saha; D. Nagarjuna Rao; A. Jayakumar; Saji Mohandas; V. S. Prasad (Natural Hazards, 2024)

Hybrid nanomaterials for efficient hexavalent chromium removal from waste water: activated charcoal sheet modification through polypyrrole and silver nanoparticles - Surender; Chandra Mohan; Rakesh Kumar; Rajender S. Varma (Nanotechnology for Environmental Engineering, 2024)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

MIG1, TUP1 and NRG1 mediated yeast to hyphal morphogenesis inhibition in Candida albicans by ganciclovir - Tanjila Gavandi; Shivani Patil; Sargun Basrani; Shivanand Yankanchi; Sayali Chougule; S. Mohan Karuppayil; Ashwini Jadhav (Brazilian Journal of Microbiology, 2024)

Remote sensing-based mangrove blue carbon assessment in the Asia-Pacific: A systematic review - Abhilash Dutta Roy; Pavithra S. Pitumpe Arachchige; Michael S. Watt; Apoorwa Kale; Mollie Davies; Joe Eu Heng; Redeat Daneil; G.A. Pabodha Galgamuwa; Lara G. Moussa; Kausila Timsina; Ewane Basil Ewane; Kerrylee Rogers; et al. (Science of The Total Environment, 2024)

Ecotourism and mangrove conservation in Southeast Asia: Current trends and perspectives - Austin Blanton; Ewane Basil Ewane; Freddie McTavish; Michael S. Watt; Kerrylee Rogers; Redeat Daneil; Irene Vizcaino; Ana Novo Gomez; Pavithra S. Pitumpe Arachchige; Shalini A.L. King; G.A. Pabodha Galgamuwa; Martha Lucia Palacios Peñaranda; et al. (Journal of Environmental Management, 2024)

Efficiency and mechanistic insights of photocatalytic decomposition of tetracycline and rhodamine B utilizing Z-scheme g-C3N4/SnWO4 heterostructures under visible light irradiation - Ramu Boddepalli; Thirumala Rao Gurugubelli; Pammi S.V.N; V.S. Bhagavan Netheti; S. Yusub; Mohan Rao Tamtam; Ravindranadh Koutavarapu; Lalitha Saranya Pidaparthy (Environmental Research, 2024)

Isoxazolyl-urea derivative evokes apoptosis and paraptosis by abrogating the Wnt/β-catenin axis in colon cancer cells - Rajaghatta N. Suresh; Young Yun Jung; Kachigere B. Harsha; Chakrabhavi Dhananjaya Mohan; Kwang Seok Ahn; Kanchugarakoppal S. Rangappa (Chemico-Biological Interactions, 2024)

Elevated Complement Activation Fragments and C1q-Binding Circulating Immune Complexes in Varied Phases of Chikungunya Virus Infection - Rewati Kasbe; Anuradha S. Tripathy; Mohan R. Wani; Jayati Mullick (Current Microbiology, 2024)

Nutrient dynamics in small west-flowing tropical mountainous rivers of India - S. Kiran Kumar Reddy; Harish Gupta; Vamshi Krishna Gandla; D. Venkat Reddy; Rama Mohan Kurakalva; Devender Kumar (Applied Geochemistry, 2024)

Redox cycling-based signal amplification at alkanethiol modified nanoporous gold interdigitated microelectrodes - Yi Liu; Ajith Mohan Arjun; Sean Webb; Monica Wolfe; Jorge L. Chávez; Nathan S. Swami (Analytica Chimica Acta, 2024)

Soil Carbon Sequestration and Agronomic Productivity as Influenced by the Long-Term Organic and Inorganic Fertilisation Under the Upland Rice–Wheat System in Vertisols of Central India - Ch. Srinivasarao; Sumanta Kundu; D. P. Dubey; Rajiv Dubey; S. Rakesh; Rattan Lal; P. C. Abhilash; J. V. N. S. Prasad; G. Pratibha; Somasundaram Jayaraman; K. Mrunalini; K. A. Gopinath; et al. (Anthropocene Science, 2024)

Physiological and biochemical response in green mussel Perna viridis subjected to continuous chlorination: Perspective on cooling water discharge criteria - Bandita Badakumar; D. Inbakandan; S. Venkatnarayanan; T.V. Krishna Mohan; Y.V. Nancharaiah; N.K. Pandey; P. Veeramani; P. Sriyutha Murthy (Chemosphere, 2024)

Genetic Instability and Disease Progression of Indian Rett Syndrome Patients - Mohan Gomathi; Venkatesan Dhivya; Vijayakumar Padmavathi; Murugasamy Pradeepkumar; S. Robert Wilson; Nachimuthu Senthil Kumar; Vellingiri Balachandar (Molecular Neurobiology, 2024)

Antifungal Activity of Mefloquine Against Candida albicans Growth and Virulence Factors: Insights Into Mode of Action - Sargun T. Basrani; Nandakumar S. Kadam; Dhairyasheel V. Yadav; Shivani B. Patil; S. Mohan Karuppayil; Ashwini K. Jadhav (Current Microbiology, 2024)

Advanced techniques in leachate management - P.V. Nidheesh; Akeem Adeyemi Oladipo; Rajan Gandhimathi; S. Venkata Mohan (Process Safety and Environmental Protection, 2024)

RETRACTED: Rationally construction of 2D & 3D material on h-BN @ SnO2/TiO2 micro-sphere enables for photocatalytic debasement of textile cloth dyes in waste water treatment - A. Vasantham; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan Perumal (Environmental Research, 2024)

Diversity of culturable gut bacteria in natural aphid populations and their contribution to insecticide degradation - Mahesh S. Yandigeri; Manoj Kumar Solanki; Sanjay Yalashetti; Sampada N; Mohan M; Sivakumar G; Sunil Joshi; Satya Nand Sushil (Biocatalysis and Agricultural Biotechnology, 2024)

Phylogenic diversity of bacteria associated with potentially toxic cyanobacteria Microcystis aeruginosa: a synthesis on its bloom dynamics - Renju Mohan; Sreya S. Pillai; Aishwarya Purushothaman; Lathika Cicily Thomas; K. B. Padmakumar (Folia Microbiologica, 2024)

An ensemble deep learning approach for air quality estimation in Delhi, India - Anju S. Mohan; Lizy Abraham (Earth Science Informatics, 2024)

Amino acids rich biomass cultivation: Trophic mode influence on Chlorella Growth Factor (CGF) production - Manupati Hemalatha; S. Venkata Mohan (Algal Research, 2024)

Future perspective of nanobubble technology in dairy processing applications - F.N.U. Akshit; Ting Mao; Maneesha S. Mohan (Trends in Food Science & Technology, 2024)

Improved photocatalytic degradation of organic pollutants using green synthesized ZnO and Ni@ZnO NPs for environmental applications - N.S. Mohan; S. Bhuvaneswari; R. Anitha; V. Vijayalakshmi (Environmental Nanotechnology, Monitoring & Management, 2024)

Facile fabrication of amorphous Al/Fe based metal–organic framework as effective heterogeneous fenton catalyst for environmental remediation - Thirumoorthy Kulandaivel; Akshaya Subhramaniyan Rasappan; Kirankumar Venkatesan Savunthari; Melvin S. Samuel; Mohanraj Kumar; Hans-Uwe Dahms; Aswin Kumar Anbalagan; Gopalakrishnan Mohan; Soorathep Kheawhom; Sivarasan Ganesan (Environmental Geochemistry and Health, 2024)

Conductive materials and applied potential to augment methanogenesis for biogas upgradation: Acidogenic synergy, CO2 dynamics and sustainability analysis - Shalini Singh; Triya Mukherjee; S. Venkata Mohan (Journal of Cleaner Production, 2024)

Modulating cultivation regimes of Messastrum gracile SVMIICT7 for biomass productivity integrated with resource recovery via hydrothermal liquefaction - Boda Ravi Kiran; Pooja Singh; Sri Divya Kuravi; Kaustubha Mohanty; S. Venkata Mohan (Journal of Environmental Management, 2024)

Structurally engineered probe infused porous polymer monolith as a solid-state visual sensing platform for Cd2+ ions - Sangeetha Krishna Kumar; Satheesh Kuppusamy; Anju Pavoor Veedu; Pitchaiah Kancharlapalli Chinaraga; C V S Brahmmananda Rao; Sivaraman Nagarajan; Prabhakaran Deivasigamani; Akhila Maheswari Mohan (Journal of Environmental Chemical Engineering, 2024)

Geochemical dichotomy of Tethyan oceanic mantle and the supercontinent connection: Insights from Os isotopic signatures of mantle peridotites from Naga Hills ophiolite - A. Verencar; A. Saha; S. Ganguly; M. Satyanarayanan; M. Ram Mohan (Gondwana Research, 2024)

Decoupling acidogenic cascade via bio-electrogenic induced ABE pathway for enhanced n-butanol synthesis in Clostridium acetobutylicum ATCC-824: Bioenergetics and gene expression analysis - Vaibhav Nailwal; Triya Mukherjee; S Venkata Mohan (Chemical Engineering Journal, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Geochemical partitioning of sediment-bound phosphorous in Thrissur Kole Wetlands, Southwest India: Status of bioavailability and trophic state - P. V. Vidya; S. Rajathy; C. S. Ratheesh Kumar; S. K. Maneesh Kumar; K. B. Akhilesh; R. Mohan; A. Sudha (International Journal of Environmental Science and Technology, 2024)

An improvement in water stress tolerance in rice by altering morpho-physiological and biochemical mechanisms using root colonizing endophyte Piriformospora indica - S. Lekshmi Mohan; R. Beena; M. Joy (Vegetos, 2024)

Chemical composition and biological activities of Lonicera caprifolium L. (Caprifoliaceae) essential oil - Anjali A. Gavit; Manish B. Gagrani; Shailendra S. Gurav; M. Ayyanar; Vishal G. Beldar; Anilkumar U. Tatiya; Sanjay J. Surana; Sandip D. Firke; Mohan G. Kalaskar (Natural Product Research, 2024)

Mapping 3R and Circular Economy Policy Implementation in Asia and the Pacific - Jinesh Mohan; Choudhury Rudra Charan Mohanty; Jeffrey S. Cross; Anupam Khajuria (Circular Economy and Sustainability, 2024)

The strict regulation of HIF-1α by non-coding RNAs: new insight towards proliferation, metastasis, and therapeutic resistance strategies - Sabrean Farhan Jawad; Farag M. A. Altalbawy; Radhwan M. Hussein; Ali Abdulhussain Fadhil; Mohammed Abed Jawad; Rahman S. Zabibah; Tasneem Younus Taraki; Chakrabhavi Dhananjaya Mohan; Kanchugarakoppal S. Rangappa (Cancer and Metastasis Reviews, 2024)

Exploring bacterial diversity in Arctic fjord sediments: a 16S rRNA–based metabarcoding portrait - Bhavya Kachiprath; Solly Solomon; Jayanath Gopi; P. R. Jayachandran; Jabir Thajudeen; Manomi Sarasan; Anjali S. Mohan; Jayesh Puthumana; E. R. Chaithanya; Rosamma Philip (Brazilian Journal of Microbiology, 2024)

Techno-economic feasibility of a recycling plant for the extraction of metals and boehmite from hazardous petroleum spent catalysts - Meena Marafi; Ashish Pathak; Mohan S. Rana (Environmental Science and Pollution Research, 2024)

The status of forest carbon markets in Latin America - Austin Blanton; Midhun Mohan; G.A. Pabodha Galgamuwa; Michael S. Watt; Jorge F. Montenegro; Freddie Mills; Sheena Camilla Hirose Carlsen; Luisa Velasquez-Camacho; Barbara Bomfim; Judith Pons; Eben North Broadbent; Ashpreet Kaur; et al. (Journal of Environmental Management, 2024)

RETRACTED: Green waste immobilized Ag/Cu feather like Bi-matrix on garment dye decomposes and their bio-efficacy - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Karthikeyan perumal (Environmental Research, 2024)

RETRACTED: Pyto-Architechture of Ag, Au and Ag–Au bi-metallic nanoparticles using waste orange peel extract for enable carcinogenic Congo red dye degradation - B. Christina; K. Thanigaimani; R. Sudhakaran; S. Mohan; Natarajan Arumugam; Abdulrahman I. Almansour; Sakkarapalayam M. Mahalingam (Environmental Research, 2024)

Biorefinery-centric ethanol and oleochemical production employing Yarrowia lipolytica and Pichia farinosa - Sravya Manasa; Athmakuri Tharak; S. Venkata Mohan (Bioresource Technology, 2024)

Resolving taxonomic ambiguity and distribution of Tremoctopus gracilis (Cephalopoda: Tremoctopodidae) based on molecular evidence - Kurichithara K. Sajikumar; Geetha Sasikumar; Divya Viswambharan; Summaya Rahuman; N. S. Jeena; Nedumpally Vineesh; C. P. Binesh; K. P. Said Koya; V. Mahesh; Prathibha Rohit; P. K. Asokan; Smruthu Mohan; et al. (Marine Biology, 2024)

Unleashing the room temperature boronization: Blooming of Ni-ZIF nanobuds for efficient photo/electro catalysis of water - G. John; S. Priyadarshini; Anandha babu; Harshavardhan Mohan; Byung-Taek Oh; M. Navaneethan; P. Justin Jesuraj (Chemosphere, 2024)

Ultrasensitive and reversible NO2 gas sensor based on SnS2/TiO2 heterostructures for room temperature applications - P. Bharathi; S. Harish; M. Shimomura; M. Krishna Mohan; J. Archana; M. Navaneethan (Chemosphere, 2024)

Functional parametric influence on glutaminase free l-asparaginase production by Amycolatopsis thermoflava SFMA-103 - Cheemalamarri Chandra Sekhar; Uma Rajeswari Batchu; Ravinder Reddy Patlolla; K. Rosangzuala; Gajjala Raveena; Somarowthu Tejaswi; K. Ravichandra; Venkata Mohan S; Linga Banoth (Biocatalysis and Agricultural Biotechnology, 2024)

Clinical Utility of Pro-inflammatory Oligomeric Glycoprotein Tenascin-C in the Diagnosis of Seropositive and Seronegative Rheumatoid Arthritis - Sachin Dominic; K. S. S. Sai Baba; N. N. Sreedevi; Arshi Sanober; Liza Rajasekhar; Siraj Ahmed Khan; Noorjahan Mohammed; M. Vijaya Bhaskar; Iyyapu Krishna Mohan (Indian Journal of Clinical Biochemistry, 2024)

Mineral magnetic properties of surface soils from the Broknes and Grovnes Peninsula, Larsemann Hills, East Antarctica - G.S. Joju; Anish Kumar Warrier; Marcos A.E. Chaparro; B.S. Mahesh; Freddy Abraham Matthew; S. Anusree; Rahul Mohan (Polar Science, 2023)

Correction: Exogenous delivery of dsRNA for management of mungbean yellow mosaic virus on blackgram - K. Kamesh Krishnamoorthy; V. G. Malathi; P. Renukadevi; S. Mohan Kumar; M. Raveendran; M. Sudha; N. Manivannan; G. Karthikeyan (Planta, 2023)

Local earthquake tomography of the Cachar fold and thrust belt in lower Assam, Northeast India - Shushant Singh; G. Mohan; B. Shekar; S. K. Singh (Geo-Marine Letters, 2023)

Influence of quantity, quality, horizontal and vertical distribution of ground control points on the positional accuracy of UAV survey - Dharshan Shylesh D S; Manikandan N; Sivasankar S; Surendran D; Jaganathan R; Mohan G (Applied Geomatics, 2023)

Antibiofilm potential of gallic acid against Klebsiella pneumoniae and Enterobacter hormaechei : in-vitro and in-silico analysis - Pooja P. Rajan; Praveen Kumar; Minsa Mini; Devi Jayakumar; Parvathi Vaikkathillam; Sneha Asha; Aparna Mohan; Manjusree S (Biofouling, 2023)

Remote sensing-based assessment of mangrove ecosystems in the Gulf Cooperation Council countries: a systematic review - Marcela Rondon; Ewane Basil Ewane; Meshal M. Abdullah; Michael S. Watt; Austin Blanton; Ammar Abulibdeh; John A. Burt; Kerrylee Rogers; Tarig Ali; Ruth Reef; Rabi Mohtar; Frida Sidik; et al. (Frontiers in Marine Science, 2023)
Mangrove forests in the Gulf Cooperation Council (GCC) countries are facing multiple threats from natural and anthropogenic-driven land use change stressors, contributing to altered ecosystem conditions. Remote sensing tools can be used to monitor mangroves, measure mangrove forest-and-tree-level attributes and vegetation indices at different spatial and temporal scales that allow a detailed and comprehensive understanding of these important ecosystems. Using a systematic literature approach, we reviewed 58 remote sensing-based mangrove assessment articles published from 2010 through 2022. The main objectives of the study were to examine the extent of mangrove distribution and cover, and the remotely sensed data sources used to assess mangrove forest/tree attributes. The key importance of and threats to mangroves that were specific to the region were also examined. Mangrove distribution and cover were mainly estimated from satellite images (75.2%), using NDVI (Normalized Difference Vegetation Index) derived from Landsat (73.3%), IKONOS (15%), Sentinel (11.7%), WorldView (10%), QuickBird (8.3%), SPOT-5 (6.7%), MODIS (5%) and others (5%) such as PlanetScope. Remotely sensed data from aerial photographs/images (6.7%), LiDAR (Light Detection and Ranging) (5%) and UAV (Unmanned Aerial Vehicles)/Drones (3.3%) were the least used. Mangrove cover decreased in Saudi Arabia, Oman, Bahrain, and Kuwait between 1996 and 2020. However, mangrove cover increased appreciably in Qatar and remained relatively stable for the United Arab Emirates (UAE) over the same period, which was attributed to government conservation initiatives toward expanding mangrove afforestation and restoration through direct seeding and seedling planting. The reported country-level mangrove distribution and cover change results varied between studies due to the lack of a standardized methodology, differences in satellite imagery resolution and classification approaches used. There is a need for UAV-LiDAR ground truthing to validate country-and-local-level satellite data. Urban development-driven coastal land reclamation and pollution, climate change-driven temperature and sea level rise, drought and hypersalinity from extreme evaporation are serious threats to mangrove ecosystems. Thus, we encourage the prioritization of mangrove conservation and restoration schemes to support the achievement of related UN Sustainable Development Goals (13 climate action, 14 life below water, and 15 life on land) in the GCC countries.

Occurrence and potential harms of organochlorine pesticides (OCPs) in environment and their removal by periphyton - Cilai Tang; Zhihao Chen; Yingping Huang; Inna P. Solyanikova; S. Venkata Mohan; Hongfeng Chen; Yonghong Wu (Critical Reviews in Environmental Science and Technology, 2023)

Latent heat flux variability over the tropical Indian Ocean - Soumya Mohan; R. D. Ruchith; S. Rahul; P. R. Shanas (International Journal of Climatology, 2023)
The seasonal evolution and interannual variability of latent heat flux (LHF) over the tropical Indian Ocean (TIO) region is examined for the period 1980–2019. The seasonal distribution of LHF is dominated by the winter pattern of each hemisphere in the TIO. Climatologically high LHF is mostly confined to the Arabian Sea and Bay of Bengal regions in the north Indian Ocean and the zonal belt between 10 o S and 25 o S in the south Indian Ocean. Warm and cold phases of El‐Niño Southern Oscillation, Indian Ocean Dipole (IOD), and their co‐occurrence events leave distinct LHF signatures over the TIO. The LHF anomalies during these events are more profound than pure events with enhanced latent heat loss when the La Niña and negative IOD events coincide. The LHF anomalies associated with the wind‐evaporation‐SST feedback is prominent when positive IOD co‐occur with the El‐Niño event. Both the vertical humidity gradient and wind speed changes play substantial roles in driving LHF anomalies during the co‐occurring events of NIOD and La Niña.

Computational optimization of the performance of a heavy-duty natural gas pre-chamber engine - Xinlei Liu; Mickael Silva; Balaji Mohan; Abdullah S. AlRamadan; Emre Cenker; Hong G. Im (Fuel, 2023)

Isolation and molecular detection of endophytic actinomycetes Nocardiopsis dassonvillei DMS 1 (MH900216) from marine sea grasses with bacterial inactivation - Chackaravarthi Gnanasekaran; Ramachandran Govindan; Mohan Kumar N.; Chenthis Kanisha Chelliah; Rajivgandhi Govindan; Priya Ranganathan; Maruthupandy Muthuchamy; Franck Quero; Arulraj Arunachalam; Mangalaraja Ramalinga Viswanathan; Naiyf S. Alharbi; Manoharan Natesan (Biocatalysis and Agricultural Biotechnology, 2023)

Development of non-stationary temperature duration frequency curves for Indian mainland - Meera G. Mohan; Adarsh S. (Theoretical and Applied Climatology, 2023)

Exogenous delivery of dsRNA for management of mungbean yellow mosaic virus on blackgram - K. Kamesh Krishnamoorthy; V. G. Malathi; P. Renukadevi; S. Mohan Kumar; M. Raveendran; M. Sudha; N. Manivannan; G. Karthikeyan (Planta, 2023)

Forest dynamics along altitudinal gradient covering treeline ecotone of Indian Western Himalaya - Renu Rawal; Vikram S. Negi; Lalit Mohan Tewari (Biologia, 2023)

Hypoglycemic, anti-inflammatory, and anti-aging potential of Canthium coromandelicum (Burm.f.) Alston leaf extracts: In vitro and in silico ADMET studies - Singamoorthy Amalraj; Shailendra S. Gurav; Mohan G Kalaskar; Alfred Maroyi; Muniappan Ayyanar (South African Journal of Botany, 2023)

Analyzing the streamflow teleconnections of greater Pampa basin, Kerala, India using wavelet coherence - Meera G. Mohan; S. Fathima; S. Adarsh; Nimisha Baiju; G.R. Arathy Nair; S. Meenakshi; M. Soumya Krishnan (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Data driven approach for the management of wind and solar energy integrated electrical distribution network with high penetration of electric vehicles - Manuel S. Mathew; Mohan Lal Kolhe; Surya Teja Kandukuri; Christian W. Omlin (Journal of Cleaner Production, 2023)

Electrogenic engineered flow through tri-phasic wetland system for azo dye treatment: Microbial dynamics and functional metagenomics - Dileep Kumar Yeruva; Venkata Mohan S (Environmental Pollution, 2023)

Experimental safety testing confirms that the NSAID nimesulide is toxic to Gyps vultures in India - Karikalan Mathesh; Kesavan Manickam; John W. Mallord; K. Mahendran; Asok Kumar M.; Debasish Saikia; Chandra Mohan S.; Beena V.; Sree Lakshmi P.; Nikita Prakash; Rohan Shringarpure; Abhijit M. Pawde; et al. (Environmental Toxicology and Pharmacology, 2023)

Effect of acute cold exposure on cardiac mitochondrial function: role of sirtuins - Mithra. S. Mohan; S. S. Aswani; N. S. Aparna; P. T. Boban; P. R. Sudhakaran; K. Saja (Molecular and Cellular Biochemistry, 2023)

Supporting conservationists’ mental health through better working conditions - Thomas Pienkowski; Aidan Keane; Sofia Castelló y Tickell; Emiel de Lange; Mirjam Hazenbosch; Munib Khanyari; William N. S. Arlidge; Gergő Baranyi; Stephanie Brittain; Vena Kapoor; Vik Mohan; Sarah Papworth; et al. (Conservation Biology, 2023)
Biodiversity conservation work can be challenging but rewarding, and both aspects have potential consequences for conservationists’ mental health. Yet, little is known about patterns of mental health among conservationists and its associated workplace protective and risk factors. A better understanding might help improve working conditions, supporting conservationists’ job satisfaction, productivity, and engagement, while reducing costs from staff turnover, absenteeism, and presenteeism. We surveyed 2311 conservation professionals working in 122 countries through an internet survey shared via mailing lists, social media, and other channels. We asked them about experiences of psychological distress, working conditions, and personal characteristics. Over half were from and worked in Europe and North America, and most had a university‐level education, were in desk‐based academic and practitioner roles, and responded in English. Heavy workload, job demands, and organizational instability were linked to higher distress, but job stability and satisfaction with one's contributions to conservation were associated with lower distress. Respondents with low dispositional and conservation‐specific optimism, poor physical health, and limited social support, women, and early‐career professionals were most at risk of distress in our sample. Our results flag important risk factors that employers could consider, although further research is needed among groups underrepresented in our sample. Drawing on evidence‐based occupational health interventions, we suggest measures that could promote better working conditions and thus may improve conservationists’ mental health and abilities to protect nature.

Guillain Barre Syndrome as a Complication of Infections Including COVID-19: a Review - Shruti V. Kurup; Pratiksha M. Patil; Sonam S. Atkari; Sakshi R. Divate; Baban S. Thawkar; Mohan K. Kale (Current Pharmacology Reports, 2023)

Isotopic Turnover and Fractionation of δ15N and δ13C in Captive Pseudopleuronectes americanus (Walbaum) - Addie L. Binstock; Audrey S. Fox; John A. Mohan (Fishes, 2023)
Stable isotope ratios of nitrogen (δ15N) and carbon (δ13C) are ubiquitous ecological tracers used to elucidate an organism’s diet and habitat. However, the application of stable isotope ratios to reconstruct a consumer’s ecology relies upon accurate rates for isotopic turnover at both a tissue and species-specific level. This study estimated isotope turnover rates and trophic discrimination factors in four different tissues (liver, digestive tissue, muscle, and skin) with variable metabolic activity in winter flounder Pseudopleuronectes americanus using a controlled diet-switch experiment. Differences in half-lives were noted among the tissues and between the experimental diets for both δ15N and δ13C. The experimental diets of krill and mysis had variability in nutritional composition, resulting in similar turnovers in δ15N but slower turnovers in δ13C for fish fed krill. Turnovers in both δ15N and δ13C were strongly influenced by metabolism, with the contribution reaching up to 98%, as fish exhibited minimal overall growth. The results of this study demonstrate the importance of considering differences in the catabolic activity of tissue maintenance for fish exhibiting minimal growth, as well as differences in metabolic assimilation of dietary sources that vary in their protein and lipid contents.

Implementing nationally determined contributions under the Paris Agreement: An assessment of ocean-based climate action in Caribbean Small Island Developing States - Preeya S. Mohan (Marine Policy, 2023)

Development of low-cost base isolation technique using multi-criteria optimization and its application to masonry building - Zoheb Nawaz Md; Mohan S C; Sri Kalyana Rama Jyosyula (Soil Dynamics and Earthquake Engineering, 2023)

Occurrence and risk assessment of total mercury, methylmercury and other selected trace metals in the surface sediments of the Cochin Estuary, Southwest Coast of India - Binish M.B.; Magesh N.S.; Sruthy S.; Kannan V.M.; Mahesh Mohan (Regional Studies in Marine Science, 2023)

CXCR4 expression is elevated in TNBC patient derived samples and Z-guggulsterone abrogates tumor progression by targeting CXCL12/CXCR4 signaling axis in preclinical breast cancer model - Nikita Gupta; Chakrabhavi Dhananjaya Mohan; Muthu K. Shanmugam; Young Yun Jung; Arunachalam Chinnathambi; Sulaiman Ali Alharbi; Milad Ashrafizadeh; Manas Mahale; Andreas Bender; Alan Prem Kumar; Thomas Choudary Putti; Kanchugarakoppal S. Rangappa; et al. (Environmental Research, 2023)

Natural compounds targeting nuclear receptors for effective cancer therapy - Mangala Hegde; Sosmitha Girisa; Nikunj Naliyadhara; Aviral Kumar; Mohammed S. Alqahtani; Mohamed Abbas; Chakrabhavi Dhananjaya Mohan; Sudha Warrier; Kam Man Hui; Kanchugarakoppal S. Rangappa; Gautam Sethi; Ajaikumar B. Kunnumakkara (Cancer and Metastasis Reviews, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Dynamic flood frequency analysis for west flowing rivers of Kerala, India - Meera G. Mohan; S. Adarsh (Water Security, 2023)

From coarse resolution to practical solution: GRACE as a science communication and policymaking tool for sustainable groundwater management - Li Xu; David Ferris; Xander Huggins; Jefferson S. Wong; Chinchu Mohan; Sara Sadri; Hrishikesh A. Chandanpurkar; Palash Sanyal; James S. Famiglietti (Journal of Hydrology, 2023)

Orienting biodiesel production towards sustainability and circularity by tailoring the feedstock and processes - Rachapudi Venkata Sreeharsha; Namrata Dubey; S Venkata Mohan (Journal of Cleaner Production, 2023)

Highly sensitive near room temperature operable NO2 gas-sensor for enhanced selectivity via nanoporous CuO@ZnO heterostructures - A. Govind; P. Bharathi; M. Krishna Mohan; J. Archana; S. Harish; M. Navaneethan (Journal of Environmental Chemical Engineering, 2023)

Hydrothermal processing of agar waste to levulinic acid and fermentation of hydrolysate to bioethanol - G. Suresh; Harishankar Kopperi; S. Venkata Mohan (Bioresource Technology, 2023)

Microbial degradation of organochlorine pesticide: 2,4-Dichlorophenoxyacetic acid by axenic and mixed consortium - T.K. Vanitha; G. Suresh; Murali Mohan Bhandi; Mohana Krishna Reddy Mudiam; S. Venkata Mohan (Bioresource Technology, 2023)

Co-fermenting lactic acid and glucose towards caproic acid production - Shikha Dahiya; S. Venkata Mohan (Chemosphere, 2023)

A novel biomass derived activated carbon mediated AC@ZnO/NiO bifunctional nanocatalyst to produce high-quality biodiesel from dairy industry waste oil: CI engine performance and emission - Basir Maleki; Yatish Kalanakoppal Venkatesh; S. Siamak Ashraf Talesh; Hossein Esmaeili; Sakar Mohan; Geetha R. Balakrishna (Chemical Engineering Journal, 2023)

Light-dependent biohydrogen production: Progress and perspectives - G. Suresh; Poonam Kumari; S. Venkata Mohan (Bioresource Technology, 2023)

Catalytic hydrothermal deoxygenation of sugarcane bagasse for energy dense bio-oil and aqueous fraction acidogenesis for biohydrogen production - Harishankar Kopperi; S. Venkata Mohan (Bioresource Technology, 2023)

Novel approach for the synthesis of hybrid clay-based nanopigments and their application as coloring agents - Chandra Mohan; Rajender S. Varma; Neeraj Kumari (Clean Technologies and Environmental Policy, 2023)

Assessing groundwater recharge rates, water quality changes, and agricultural impacts of large-scale water recycling - Kavita Verma; Manjari Manisha; R.M. Santrupt; T.P. Anirudha; Shubham Goswami; M. Sekhar; N. Ramesh; Mohan Kumar M S; H.N. Chanakya; Lakshminarayana Rao (Science of The Total Environment, 2023)

Bioaugmentation-assisted bioremediation and biodegradation mechanisms for PCB in contaminated environments: A review on sustainable clean-up technologies - Auwalu Hassan; Fauziah S. Hamid; Agamuthu Pariatamby; Nurul Shamsinah M. Suhaimi; Noor Maiza binti M. Razali; Kimberly N.H. Ling; Priya Mohan (Journal of Environmental Chemical Engineering, 2023)

Financing needs to achieve Nationally Determined Contributions under the Paris Agreement in Caribbean Small Island Developing States - Preeya S. Mohan (Mitigation and Adaptation Strategies for Global Change, 2023)

A review of oleogels applications in dairy foods - Bhaswati Chowdhury; Aditya Sharma; F. N. U. Akshit; Maneesha S. Mohan; Prafulla Salunke; Sanjeev Anand (Critical Reviews in Food Science and Nutrition, 2023)

Delineation of thin and discrete sand reservoir facies from shale-dominated Kopili Formation (Middle to Late Eocene) using the post-stack seismic inversion and neural network algorithm: A case study from Assam Basin, India - Satya Narayan; Rahul Singh; Anand Mohan; Kumar Vivek; Paridhi Acharya; S K Pal (Journal of Earth System Science, 2023)

Sustainable consideration for traditional textile handloom cluster/village in pollution abatement – A case study - Harishankar Kopperi; Manupati Hemalatha; Boda Ravi Kiran; J. Santhosh; S Venkata Mohan (Environmental Pollution, 2023)

Understanding acidogenesis towards green hydrogen and volatile fatty acid production – Critical analysis and circular economy perspective - Shikha Dahiya; Yaswanth Lingam; S. Venkata Mohan (Chemical Engineering Journal, 2023)

Biomass to green hydrogen (BGH2-2022) - Thallada Bhaskar; S Venkata Mohan; Siming You; Sang-Hyoun Kim; Luciana Porto de Souza Vandenberghe (Bioresource Technology, 2023)

Dairy wastewater treatment using Monoraphidium sp. KMC4 and its potential as hydrothermal liquefaction feedstock - Pooja Singh; S. Venkata Mohan; Kaustubha Mohanty (Bioresource Technology, 2023)

Heavy metal contamination in river water, sediment, groundwater and human blood, from Kanpur, Uttar Pradesh, India - Varsha Gupta; Dinesh Kumar; Anamika Dwivedi; Umesh Vishwakarma; D. S. Malik; Seema Paroha; Narendra Mohan; Neelima Gupta (Environmental Geochemistry and Health, 2023)

Understanding the distribution of antibiotic resistance genes in an urban community using wastewater-based epidemiological approach - Yamini Javvadi; S. Venkata Mohan (Science of The Total Environment, 2023)

Municipal landfill leachate remediation coupling acidogenesis and bioelectrogenesis for biohydrogen and volatile fatty acids production - Masapogu Yellappa; Omprakash Sarkar; Y.V. Rami Reddy; S. Venkata Mohan (Process Safety and Environmental Protection, 2023)

In-Silico molecular screening of natural compounds as a potential therapeutic inhibitor for Methicillin-resistant Staphylococcus aureus inhibition - Palanichamy Nandhini; Prashant Kr Gupta; Arun Kumar Mahapatra; Agneesh Pratim Das; Subhash Mohan Agarwal; Suresh Mickymaray; Abdulaziz S. Alothaim; Mariappan Rajan (Chemico-Biological Interactions, 2023)

DNA barcoding and nutritional profiling of underutilized native indigenous plant species of Karnataka, India - Bharathi Tumkur Ramasetty; Roshni Mohan Kumar; Prakash H. S (Molecular Biology Reports, 2023)

In vitro and in vivo anti-inflammatory and anti-arthritic effect of Tinospora cordifolia via modulation of JAK/STAT pathway - Genu George; G. L. Shyni; Sreelekshmi Mohan; Billu Abraham; P. Nisha; S. Ranjith; K. Rajankutty; K. G. Raghu (Inflammopharmacology, 2023)

Environmental Exposure Disparities and Neurodevelopmental Risk: a Review - Aisha S. Dickerson; Seth Frndak; Melissa DeSantiago; Ankita Mohan; Genee S. Smith (Current Environmental Health Reports, 2023)

The sea lettuce Ulva sensu lato: Future food with health-promoting bioactives - Harsha Mohan E; Madhusudan S; Revathy Baskaran (Algal Research, 2023)

Innovative pilot-scale constructed wetland-microbial fuel cell system for enhanced wastewater treatment and bioelectricity production - V. Kiran Kumar; K. Man mohan; Sreelakshmi P. Manangath; S. Gajalakshmi (Chemical Engineering Journal, 2023)

Petrogenesis of Meso-Neoarchean granitoids from the Chitradurga Greenstone Belt: Implications on crustal growth and reworking of the Dharwar Craton, southern India - M. Ram Mohan; Neal J. McNaughton; D. Srinivasa Sarma; M. Rajamanickam; Ian R. Fletcher; Simon A. Wilde; Birger Rasmussen; Bryan Krapež; S. Balakrishnan (Journal of Asian Earth Sciences, 2023)

Chemolithoautotrophic reduction of CO2 to acetic acid in gas and gas-electro fermentation systems: Enrichment, microbial dynamics, and sustainability assessment - Athmakuri Tharak; Ranaprathap Katakojwala; Sachin Kajla; S. Venkata Mohan (Chemical Engineering Journal, 2023)

Sustainable enzymatic treatment of organic waste in a framework of circular economy - Debkumar Chakraborty; Sulogna Chatterjee; Avanthi Althuri; Sankar Ganesh Palani; S. Venkata Mohan (Bioresource Technology, 2023)

Antibacterial natural products from microbial and fungal sources: a decade of advances - Sangeetha Mohan; M. S. Ajay Krishna; Manasa Chandramouli; Rangappa S. Keri; Siddappa A. Patil; Srikantamurthy Ningaiah; Sasidhar B. Somappa (Molecular Diversity, 2023)

Deep eutectic solvents in the transformation of biomass into biofuels and fine chemicals: a review - Kassian T. T. Amesho; Yuan-Chung Lin; S. Venkata Mohan; Subham Halder; Vinoth Kumar Ponnusamy; Syu-Ruei Jhang (Environmental Chemistry Letters, 2023)

Efficacy of novel insecticides and their combinations against pink bollworm, Pectinophora gossypiella (Saunders) (Lepidoptera: Gelechiidae) in cotton - V. Chinna Babu Naik; Mohan K. Narode; Sujit Kumbhare; Dilip Shriram Ghongade; T. N. Madhu; J. S. V. Murthy; Nandini Gokte-Narkhedkar; Y. G. Prasad (International Journal of Tropical Insect Science, 2023)

Utility of common variance of equally-weighted variables for GIS-based landslide susceptibility mapping at the eastern Himalaya - S K Som; Saibal Ghosh; Soumitra Dasgupta; N Thrideep Kumar; J N Hindayar; Murali Mohan; P Dasarwar; Snehasis Bhattacharya (Journal of Earth System Science, 2023)

Facile construction of cost-effective zinc-aluminium polymeric framework for efficient removal of selective both drug and dye from an aqueous medium - R. Mohan Raj; Sivarasan Ganesan; S. Suganthi; S. Vignesh; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; Raja Venkatesan; V. Raj; Huang-Mu Lo (Chemosphere, 2023)

Evaluation of five high-resolution global model rainfall forecasts over India during monsoon 2020 - Raghavendra Ashrit; Mohan S Thota; Anumeha Dube; Kondapalli Niranjan Kumar; S Karunasagar; Sushant Kumar; Harvir Singh; Rajasekhar Meka; R Phani Murali Krishna; Ashis K Mitra (Journal of Earth System Science, 2022)

Gut–Brain Axis, Neurodegeneration and Mental Health: A Personalized Medicine Perspective - Alisha Chunduri; S. Deepak Mohan Reddy; M. Jahanavi; C. Nagendranatha Reddy (Indian Journal of Microbiology, 2022)

Recycling of platinum group metals from exhausted petroleum and automobile catalysts using bioleaching approach: a critical review on potential, challenges, and outlook - Ashish Pathak; Hanadi Al-Sheeha; R. Navvamani; Richa Kothari; Meena Marafi; Mohan S. Rana (Reviews in Environmental Science and Bio/Technology, 2022)

DNA Barcode and Phylogenetic Analysis of Serranidae Fish (subfamily: Epinephelinae) From a Tropical Island Ecosystem of the Indian Ocean - V. Sachithanandam; N. Muruganandam; D.S. Sayi; Trivesh S. Mayekar; P. M. Mohan (Thalassas: An International Journal of Marine Sciences, 2022)

Heterogeneous catalyst SiO2–LaCl3·7H2O: characterization and microwave-assisted green synthesis of α-aminophosphonates and their antimicrobial activity - S. K. Thaslim Basha; Reddi Mohan Naidu Kalla; M. Varalakshmi; H. Sudhamani; Rama Moorthy Appa; Sung Chul Hong; Chamarthi Naga Raju (Molecular Diversity, 2022)

Molecular epidemiology on seasonal variation of yellow mosaic disease incidence in blackgram (Vigna mungo L. Hepper) with its vector Bemisia tabaci - Kamesh Krishnamoorthy Kalyankumar; V. G. Malathi; P. Renukadevi; Mohan Kumar S; N. Manivannan; S. G. Patil; G. Karthikeyan (International Journal of Biometeorology, 2022)

A catchment scale assessment of water balance components: a case study of Chittar catchment in South India - Dinagarapandi Pandi; Saravanan Kothandaraman; K. S. Kasiviswanathan; Mohan Kuppusamy (Environmental Science and Pollution Research, 2022)

Nutritional Crispy from Fish Scales for Human Diet - K. R. Sreelakshmi; Rehana Raj; S. Remya; V. A. Minimol; C. O. Mohan; George Ninan (Journal of Aquatic Food Product Technology, 2022)

DNA interaction, anticancer, cytotoxicity and genotoxicity studies with potential pyrazine-bipyrazole dinuclear µ-oxo bridged Au(III) complexes - Darshana N. Kanthecha; Bhupesh S. Bhatt; Mohan N. Patel; Foram U. Vaidya; Chandramani Pathak (Molecular Diversity, 2022)

Development and evaluation of India’s first intraspecific Gossypium barbadense cotton recombinant inbred mapping population for extra-long staple fibre traits - S. ANJAN GOWDA; ISHWARAPPA S. KATAGERI; N. V. MOHAN KUMAR; RAJESH S. PATIL (Journal of Genetics, 2022)

Feasibility of bioleaching integrated with a chemical oxidation process for improved leaching of valuable metals from refinery spent hydroprocessing catalyst - Ashish Pathak; Mohan S. Rana; Hanadi Al-Sheeha; Rajasekaran Navvmani; Hanan M. Al-Enezi; Sakeena Al-Sairafi; Jayshree Mishra (Environmental Science and Pollution Research, 2022)

Mechanism underpinning the sharpening of orientation and spatial frequency selectivities in the tree shrew (Tupaia belangeri) primary visual cortex - Yamni S. Mohan; Sivaram Viswanathan; Jaikishan Jayakumar; Errol K. J. Lloyd; Trichur R. Vidyasagar (Brain Structure and Function, 2022)

Human Health Risk Assessment due to Solvent Exposure from Pharmaceutical Industrial Effluent: Deterministic and Probabilistic Approaches - S. Mohan; S. Sruthy (Environmental Processes, 2022)

Micro/nano-plastics occurrence, identification, risk analysis and mitigation: challenges and perspectives - Boda Ravi Kiran; Harishankar Kopperi; S. Venkata Mohan (Reviews in Environmental Science and Bio/Technology, 2022)

Vertical distribution of PM10 and PM2.5 emission sources and chemical composition during winter period in Delhi city - R. Shanmuga Priyan; Anju Elizbath Peter; Jyothi S. Menon; Mohan George; S. M. Shiva Nagendra; Mukesh Khare (Air Quality, Atmosphere & Health, 2022)

Evaluation of the programmed death-ligand 1 mRNA expression and immunopositivity and their correlation with survival outcomes in Indian lung cancer patients - Sachin Kumar; Monu Pandey; Ishfaq A. Mir; Abhirup Mukhopadhyay; Surender K. Sharawat; Deepali Jain; Jyoutishman Saikia; Prabhat S. Malik; Sunil Kumar; Anant Mohan (Human Cell, 2022)

Effects of three strains of Pseudomonas fluorescens to soil-borne fungal pathogens and silkworm, Bombyx mori - Hilda Sundar; Sweatha S. Mohan; Ayyappan Sornam; Geetha Sivanandam; Chandrasehar Govindan (International Journal of Tropical Insect Science, 2021)

Occurrence of the supposedly endemic Australian azooxanthellate coral Astrangia woodsi Wells, 1955 in the eastern Arabian Sea - Divya Viswambharan; K. R. Sreenath; S. Jasmine; K. K. Joshi; C. R. Sreeraj; Smruthu Mohan; Prathibha Rohit (Marine Biodiversity, 2021)

Biomass and vegetation carbon stock in mangrove forests of the Andaman Islands, India - P. Ragavan; Sanjeev Kumar; K. Kathiresan; P. M. Mohan; R. S. C. Jayaraj; K. Ravichandaran; T. S. Rana (Hydrobiologia, 2021)

Belowground community turnover accelerates the decomposition of standing dead wood - Mark A. Bradford; Daniel S. Maynard; Thomas W. Crowther; Paul T. Frankson; Jacqueline E. Mohan; Corinna Steinrueck; G. F. (Ciska) Veen; Joshua R. King; Robert J. Warren (Ecology, 2021)
Standing dead trees (snags) decompose more slowly than downed dead wood and provide critical habitat for many species. The rate at which snags fall therefore influences forest carbon dynamics and biodiversity. Fall rates correlate strongly with mean annual temperature, presumably because warmer climates facilitate faster wood decomposition and hence degradation of the structural stability of standing wood. These faster decomposition rates coincide with turnover from fungal‐dominated wood decomposer communities in cooler forests to codomination by fungi and termites in warmer regions. A key question for projecting forest dynamics is therefore whether temperature effects on wood decomposition arise primarily because warmer conditions facilitate faster decomposer metabolism, or are also influenced indirectly by belowground community turnover (e.g., termites exert additional influence beyond fungal‐plus‐bacterial mediated decomposition). To test between these possibilities, we simulate standing dead trees with untreated wooden posts and follow them in the field across 5 yr at 12 sites, before measuring buried, soil–air interface and aerial post sections to quantify wood decomposition and organism activities. High termite activities at the warmer sites are associated with rates of postfall that are three times higher than at the cooler sites. Termites primarily consume buried wood, with decomposition rates greatest where termite activities are highest. However, where higher microbial and termite activities co‐occur, they appear to compensate for one another first, and then to slow decomposition rates at their highest activities, suggestive of interference competition. If the range of microbial and termite codomination of wood decomposer communities expands under climate warming, our data suggest that expansion will accelerate snag fall with consequent effects on forest carbon cycling and biodiversity in forests previously dominated by microbial decomposers.

Ensuring the adaptive potential of Coastal wetlands of India- the need of the hour for sustainable management - P. Ragavan; K. Kathiresan; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; T. S. Rana (Wetlands Ecology and Management, 2021)

Prevalence of Y chromosome microdeletion in north Indian infertile males with spermatogenesis defect - HIMANSHU SHARMA; UJJAWAL SHARMA; SANTOSH KUMAR; SHRAWAN KUMAR SINGH; RAVI MOHAN S. MAVADURU; RAJENDRA PRASAD (Journal of Genetics, 2021)

Multi-drug resistant (MDR), extended spectrum beta-lactamase (ESBL) producing and carbapenem resistant Escherichia coli in rescued Sloth bears (Melursus ursinus), India - O. R. VinodhKumar; M. Karikalan; S. Ilayaraja; Arun A. Sha; B. R. Singh; D. K. Sinha; S. Chandra Mohan; B. S. Pruthvishree; A. M. Pawde; A. K. Sharma (Veterinary Research Communications, 2021)

The Carbonic Anhydrase Inhibitor E7070 Sensitizes Glioblastoma Cells to Radio- and Chemotherapy and Reduces Tumor Growth - Silvia A. Teixeira; Mariano S. Viapiano; Augusto F. Andrade; Mohan S. Nandhu; Julia A. Pezuk; Lucas T. Bidinotto; Veridiana K. Suazo; Luciano Neder; Carlos G. Carlotti; Aline P. Becker; Luiz Gonzaga Tone; Carlos A. Scrideli (Molecular Neurobiology, 2021)

Evaluating homogeneity of monsoon rainfall in Saraswati River basin of Gujarat, India - Deepesh Machiwal; B S Parmar; Sanjay Kumar; Hari Mohan Meena; B S Deora (Journal of Earth System Science, 2021)

Eliciting heavy metal contamination on selected native organisms from Cochin estuary using contemporary biomarker approach - N D Don Xavier; S Bijoy Nandan; P R Jayachandran; K V Neethu; D Mohan; S R Marigoudar (Journal of Earth System Science, 2021)

Genetic Enhancement in Mungbean (Vigna radiata) as Revealed by Genome-Wide Mapped Microsatellite Markers - Aditya Pratap; Chandra Mohan Singh; Sanjeev Gupta; Ajeet Kumar Gupta; Revanappa S. Birader; Umashanker Prajapati; Rakhi Tomar; Narendra Pratap Singh (Agricultural Research, 2021)

Milk fat: opportunities, challenges and innovation - Maneesha S. Mohan; Tom F. O’Callaghan; Phil Kelly; Sean A. Hogan (Critical Reviews in Food Science and Nutrition, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Green mussel (Perna viridis L.) farming in India: an analysis of major growth milestones, recent decline due to disease incidence, and prospects for revival - Shinoj Parappurathu; N. K. Sanil; P. K. Asokan; S. R. Krupesha Sharma; M. A. Pradeep; Shelton Padua; Suja Gangadharan; Gishnu Mohan; Prasanna Kumar Patil (Aquaculture International, 2021)

Meeting Report: N-Nitrosamine Impurity Control Strategies in the Pharmaceutical and Biotechnology Industries - Scott W. Roberts; Andrew Lennard; Ganapathy Mohan; James Bernstein; Nina S. Cauchon; Steve Cole; Noreen Curristin; Kim Huynh-Ba; Christine N. Kolz; Cheenu Murti; Kin Tang (The AAPS Journal, 2021)

Optimal Design of Barrage Profile on Anisotropic Soil Using Multi‐Objective Optimization Approach - Arjun Prasad; Raj Mohan Singh; S. K. Duggal (Water Resources Management, 2021)

Litter degradation in evergreen forests of southern Western Ghats - M. P. Krishna; V. G. Gopikrishna; Aswathy K. Vijayan; S. Arun Sasi; Mahesh Mohan (Tropical Ecology, 2021)

SARS-CoV-2 Infection in the Central and Peripheral Nervous System-Associated Morbidities and Their Potential Mechanism - Mohan Kumar Muthu Karuppan; Dinesh Devadoss; Madhavan Nair; Hitendra S. Chand; Madepalli K. Lakshmana (Molecular Neurobiology, 2021)

Casein (CSN) gene variants and parity affect the milk protein traits in crossbred (Bos taurus x Bos indicus) cows in sub-tropical climate - Govind Mohan; Anshuman Kumar; Suhail Hakeem Khan; N. Anand Kumar; Suman Kapila; S. S. Lathwal; Monika Sodhi; S. K. Niranjan (Tropical Animal Health and Production, 2021)

Differentially expressed miR-20, miR-21, miR-100, miR-125a and miR-146a as a potential biomarker for prostate cancer - Mohan Damodaran; Mohanapriya Chinambedu Dandapani; SimonDuraiRaj; SandhyaSundaram; S. VenkatRamanan; Ilangovan Ramachandran; Vettriselvi Venkatesan (Molecular Biology Reports, 2021)

SSR markers assay-based establishment of distinctness, uniformity and stability of dolichos bean [Lablab purpureus (L.) Sweet var. Lignosus] advanced breeding lines and elite germplasm accessions - Shrikrishna P. Desai; S. Ramesh; P. V. Vaijayanthi; A. Mohan Rao; B. R. Chandana; Basanagouda Gonal (Genetic Resources and Crop Evolution, 2021)

A novel barcode system for rapid identification of rice (Oryza sativa L.) varieties using agro-morphological descriptors and molecular markers - M. Bhargavi; K. Maneesha; D. M. Withanawasam; Kavitha R. Aratikatla; S. Himabindu; M. Prashanth; P. Shanthi; Madhavi L. Kommana; D. Mohan Reddy; B. Ravindra Reddy; Lakshminarayana R. Vemireddy (Molecular Biology Reports, 2021)

Fluorescence, DNA Interaction and Cytotoxicity Studies of 4,5-Dihydro-1H-Pyrazol-1-Yl Moiety Based Os(IV) Compounds: Synthesis, Characterization and Biological Evaluation - Bharat H. Pursuwani; Bhupesh S. Bhatt; Foram U. Vaidya; Chandramani Pathak; Mohan N. Patel (Journal of Fluorescence, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Magnetic properties of surface sediments in Schirmacher Oasis, East Antarctica: spatial distribution and controlling factors - Anish Kumar Warrier; Joju George Sebastian; K. Amrutha; A. S. Yamuna Sali; B. S. Mahesh; Rahul Mohan (Journal of Soils and Sediments, 2021)
Purpose We investigated the magnetic properties (abundance, grain size, and mineralogy) of iron oxides present in Lake L-55 sediments, Schirmacher Oasis, East Antarctica, with an aim to understand their spatial distribution and the underlying mechanisms that control their formation and distribution. Methods Twenty-five surficial sediments retrieved from different parts of Lake L-55 were subjected to the entire range of environmental magnetic (magnetic susceptibility, anhysteretic remanent magnetization (ARM), isothermal remanent magnetization (IRM)) measurements (at different field strengths). Inter-parametric ratios ( χ ARM /SIRM, χ ARM / χ lf , χ ARM / χ fd , IRM 20 mT /SIRM, IRM 20 mT /ARM, S -ratio, L -ratio) provided insights into the magnetic properties (abundance, grain size, and mineralogy of iron oxides). Scanning electron microscopic-energy dispersive X-ray spectroscopic (SEM-EDS) analysis was performed on magnetic extracts from a few sediments. Besides, organic matter (%) was also calculated for the sediment samples. Principal component analysis was performed to gain information on the presence of different components and their relative dominance. Results The iron oxides are strongly magnetic (high values of concentration-dependent parameters). The principal iron oxide is magnetite ( S -ratio > 0.90) which is coarse-grained (multi-domain (MD) and stable single-domain (SSD) grains), and there is no influence of authigenic greigite, bacterial magnetite, and anthropogenic magnetite. The mineralogy is confirmed by SEM-EDS data. The iron oxides are of different grain sizes, and their contribution is in the order of MD > SSD > SP as shown by the principal component analysis. Pedogenic iron oxide minerals seem to be present in the samples whose formation is due to the oxidation of magnetite into hematite. However, they are of SSD size and not SP, suggesting that the intensity of pedogenesis is not sufficient to form SP grains. Conclusion The iron oxide minerals are mainly terrigenous, and the biogenic activity within the lake is not sufficient to modify the ferrimagnetic minerals. Spatial distribution patterns suggest the non-uniform distribution of magnetite/titanomagnetite of varying sizes in the lake basin which is transported by both melt water streams and winds.

Breeding potential of crosses derived from parents differing in fruiting habit traits in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh (Genetic Resources and Crop Evolution, 2021)

Terminalia arjuna Extract Attenuates Isoproterenol-Induced Cardiac Stress in Wistar Rats via an Anti-Apoptotic Pathway - Mohan Manu Thangaraju; Anand Tamatam; Pratiksha V. Bhat; Uma Maheswari Deshetty; S. T. Babusha; Farhath Khanum (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Observational aspects of tropical mesoscale convective systems over southeast India - A Madhulatha; M Rajeevan; T S Mohan; S B Thampi (Journal of Earth System Science, 2020)

Vertical distributions of the microscopic morphological characteristics and elemental composition of aerosols over India - Mukunda M. Gogoi; Roseline C. Thakur; Sahina Gazi; Vijayakumar S. Nair; Rahul Mohan; S. Suresh Babu (Journal of Atmospheric Chemistry, 2020)

Haemato-biochemical alterations and oxidative stress associated with naturally occurring porcine circovirus2 infection in pigs - J. B. Rajesh; S. Rajkhowa; U. Dimri; H. Prasad; N. H. Mohan; L. Hmar; K. Sarma; G. E. Chethan; P. Behera; G. Jaganmohanarao; S. Behera; Zosangpuii (Tropical Animal Health and Production, 2020)

First record of off-season flowering in Populus deltoides from India: paradigm of climate change indicator - Garima Thapliyal; Ramu S. Vemanna; Prashant Mohan Pawar; Santan Barthwal; Rajendra K. Meena; Shailesh Pandey; Maneesh S. Bhandari (International Journal of Biometeorology, 2020)

The mechanisms of biochar interactions with microorganisms in soil - Andrey V. Gorovtsov; Tatiana M. Minkina; Saglara S. Mandzhieva; Leonid V. Perelomov; Gerhard Soja; Inna V. Zamulina; Vishnu D. Rajput; Svetlana N. Sushkova; Dinesh Mohan; Jun Yao (Environmental Geochemistry and Health, 2020)

Role of Intra-Seasonal Variability in the Indian Summer Monsoon on the Hydration and Dehydration of the Upper Troposphere - K. N. Uma; T. S. Mohan; Subrata Kumar Das (Theoretical and Applied Climatology, 2020)

Multifractal description of streamflow and suspended sediment concentration data from Indian river basins - S. Adarsh; Drisya S. Dharan; A. R. Nandhu; B. Anand Vishnu; Vysakh K. Mohan; M. Wątorek (Acta Geophysica, 2020)

Individuals in urban dwelling primate species face unequal benefits associated with living in an anthropogenic environment - Pascal R. Marty; Krishna N. Balasubramaniam; Stefano S. K. Kaburu; Josephine Hubbard; Brianne Beisner; Eliza Bliss-Moreau; Nadine Ruppert; Małgorzata E. Arlet; Shahrul Anuar Mohd Sah; Ahmad Ismail; Lalit Mohan; Sandeep K. Rattan; et al. (Primates, 2020)

Random Walk Particle Tracking Embedded Cellular Automata Model for Predicting Temporospatial Variations of Chlorine in Water Distribution Systems - G. R. Abhijith; S. Mohan (Environmental Processes, 2020)

Adaptive Neuro-Fuzzy Inference System-Based Exploration of the Interrelationships of 25-Hydroxyvitamin D, Calcium, Phosphorus with Parathyroid Hormone Production - Iyyapu Krishna Mohan; Siraj Ahmed Khan; D. Shiva Krishna; M. Vijaya Bhaskar; K. S. S. Sai Baba; Tajamul Hussain; Salman A. Alrokayan; Shaik Mohammad Naushad (Indian Journal of Clinical Biochemistry, 2020)

Targeting acquired oncogenic burden in resilient pancreatic cancer: a novel benefit from marine polyphenols - Sheeja Aravindan; Dinesh Babu Somasundaram; Somasundaram T. Somasundaram; Mohan Natarajan; Terence S. Herman; Natarajan Aravindan (Molecular and Cellular Biochemistry, 2019)

Regression-Based Integrated Bi-sensor SAR Data Model to Estimate Forest Carbon Stock - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. Santra Mitra; C. Jeganathan (Journal of the Indian Society of Remote Sensing, 2019)

Genetics of fruit yield and its component traits under different fruiting habit backgrounds in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh; B. Bhavani; Pranesh (Journal of Genetics, 2019)

Magnetotellurics Study to Identify Subsurface Resistivity Structure in the Eastern Part of Kachchh (Little Rann Area) of Gujarat, India - Peush Chaudhary; Kapil Mohan; B. S. Chaudhary (Pure and Applied Geophysics, 2019)

Recombinant Partial Conglutinin of Buffalo and Nilgai In Vitro Can Mimic the Functions of Native Conglutinin In Vivo - D. Ramesh; S. Chandra Mohan; Mohini Saini; Sasmita Barik; M. Shynu; Asit Das; Anil Kumar Sharma; Vinod Kumar Chaturvedi; Praveen Kumar Gupta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Differences in CAPE between wet and dry spells of the monsoon over the southeastern peninsular India - T. S. Mohan; T. N. Rao; M. Rajeevan (Meteorology and Atmospheric Physics, 2019)

Triclosan in Treated Wastewater from a City Wastewater Treatment Plant and its Environmental Risk Assessment - S. Mohan; P. Balakrishnan (Water, Air, & Soil Pollution, 2019)

Accounting tropical forest carbon stock with synergistic use of space-borne ALOS PALSAR and COSMO-Skymed SAR sensors - Suman Sinha; A. Santra; A. K. Das; L. K. Sharma; Shiv Mohan; M. S. Nathawat; S. S. Mitra; C. Jeganathan (Tropical Ecology, 2019)

Integrated phosphorus management in maize–chickpea cropping system on alkaline Fluvisol - M. S. Venkatesh; K. K. Hazra; P. K. Ghosh; Mohan Singh (Nutrient Cycling in Agroecosystems, 2019)

Overview of genomics and post-genomics research on type 2 diabetes mellitus: Future perspectives and a framework for further studies - Battini Mohan Reddy; Rayabarapu Pranavchand; S A A Latheef (Journal of Biosciences, 2019)

Generalised extreme value model with cyclic covariate structure for analysis of non-stationary hydrometeorological extremes - R S Jagtap; V K Gedam; Mohan M Kale (Journal of Earth System Science, 2019)

63K SNP chip based linkage mapping and QTL analysis for fibre quality and yield component traits in Gossypium barbadense L. cotton - N. V. Mohan Kumar; Ishwarappa S. Katageri; S. Anjan Gowda; Sateesh Adiger; Satish Kumar Yadava; V. B. Reddy Lachagari (Euphytica, 2019)

Presence of the Wondrous Jewel Squid Histioteuthis miranda (Cephalopoda: Histioteuthidae) in the Eastern Arabian Sea and Determination of its Age from Statoliths - K. K. Sajikumar; V. Venkatesan; C. P. Binesh; Gishnu Mohan; N. K. Sanil; V. Kripa; K. S. Mohamed (Thalassas: An International Journal of Marine Sciences, 2018)

Hepcidin and Ferritin: Important Mediators in Inflammation Associated Anemia in Systemic Lupus Erythematosus Patients - Neeraja Kunireddy; Rachel Jacob; Siraj Ahmed Khan; B. Yadagiri; K. S. S. Sai Baba; I. Rajendra Vara Prasad; Iyyapu Krishna Mohan (Indian Journal of Clinical Biochemistry, 2018)

Biomass production, carbon sequestration and nutrient characteristics of 22-year-old support trees in black pepper (Piper nigrum. L) production systems in Kerala, India - T. K. Kunhamu; S. Aneesh; B. Mohan Kumar; V. Jamaludheen; A. K. Raj; P. Niyas (Agroforestry Systems, 2018)

Frequency of Heterotic Hybrids in Relation to Parental Genetic Divergence and General Combining Ability in Dolichos Bean - C. M. Keerthi; S. Ramesh; M. Byregowda; A. Mohan Rao (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Mangrove floristics of the Andaman and Nicobar Islands: critical review and current scenario - P. Ragavan; P. M. Mohan; Alok Saxena; R. S. C. Jayaraj; K. Ravichandran; Mani Saxena (Marine Biodiversity, 2018)

Purification and Characterization of Anti-cancer l-Glutaminase of Bacillus cereus Strain LC13 - Sunil S. More; Radhika Swamy; Niveditha Mohan; Markuli Navyashree; Bhavya Janardhan; Francois N. Niyonzima (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Assessing Breeding Potential of Three-Way Cross and Double-Cross Hybrids in Chilli (Capsicum annuum) - T. Lakshmi Pathy; A. Mohan Rao; S. Ramesh (Agricultural Research, 2018)

Zingiber cernuum (Zingiberaceae) essential oil as effective larvicide and oviposition deterrent on six mosquito vectors, with little non-target toxicity on four aquatic mosquito predators - Mohan Rajeswary; Marimuthu Govindarajan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Curzerene, trans-β-elemenone, and γ-elemene as effective larvicides against Anopheles subpictus, Aedes albopictus, and Culex tritaeniorhynchus: toxicity on non-target aquatic predators - Marimuthu Govindarajan; Mohan Rajeswary; Sengamalai Senthilmurugan; Periasamy Vijayan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Boswellia ovalifoliolata (Burseraceae) essential oil as an eco-friendly larvicide? Toxicity against six mosquito vectors of public health importance, non-target mosquito fishes, backswimmers, and water bugs - Giovanni Benelli; Mohan Rajeswary; Periasamy Vijayan; Sengamalai Senthilmurugan; Naiyf S. Alharbi; Shine Kadaikunnan; Jamal M. Khaled; Marimuthu Govindarajan (Environmental Science and Pollution Research, 2018)

Spectral Overlap Correction Using Weighted Deconvolution for Improved Dark Object Technique for Correction of EO1-Hyperion Data - Shailesh S. Deshpande; Arun B. Inamdar; Krishna Mohan Buddhiraju (Journal of the Indian Society of Remote Sensing, 2018)

Direct and indirect influences of intercrops on the coconut defoliator Opisina arenosella - K. S. Shameer; M. Nasser; Chandrika Mohan; Ian C. W. Hardy (Journal of Pest Science, 2018)

Circulating genotypes of Pneumocystis jirovecii and its clinical correlation in patients from a single tertiary center in India - Y. Singh; B. R. Mirdha; R. Guleria; S. Khalil; A. Panda; R. Chaudhry; A. Mohan; S. K. Kabra; L. Kumar; S. K. Agarwal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Comparative flood area analysis of C-band VH, VV, and L-band HH polarizations SAR data - R. Manavalan; Y. S. Rao; B. Krishna Mohan (International Journal of Remote Sensing, 2017)

Environmental degradation of a tropical estuary due to human interferences—a case study from southern Kerala, SW India - Shiekha E. John; T. R. Rajimol; Vishnu Mohan S; K. Maya; D. Padmalal (Arabian Journal of Geosciences, 2017)

Evaluation of Abbreviated Impactor Measurements (AIM) and Efficient Data Analysis (EDA) for Dry Powder Inhalers (DPIs) Against the Full-Resolution Next Generation Impactor (NGI) - Megha Mohan; Sau Lee; Changning Guo; S. Prasad Peri; William H. Doub (AAPS PharmSciTech, 2017)

Expression of domain III of the envelope protein from GP-78: a Japanese encephalitis virus - Sahil Kulkarni; Sandeepan Mukherjee; Krishna Mohan Padmanabha Das; Kaushiki Prabhudesai; Nupur Deshpande; Sushant Karnik; Abhay S. Chowdhary; Usha Padmanabhan (VirusDisease, 2017)

Local Contrast Based Adaptive SAR Speckle Filter - Sanjay Shitole; Mayank Sharma; Shaunak De; Avik Bhattacharya; Y. S. Rao; B. Krishna Mohan (Journal of the Indian Society of Remote Sensing, 2017)

Quantitative analysis of Sudan dye adulteration in paprika powder using FTIR spectroscopy - Santosh Lohumi; Ritu Joshi; Lalit Mohan Kandpal; Hoonsoo Lee; Moon S. Kim; Hyunjeong Cho; Changyeun Mo; Young-Wook Seo; Anisur Rahman; Byoung-Kwan Cho (Food Additives & Contaminants: Part A, 2017)

Total and methyl mercury in the water, sediment, and fishes of Vembanad, a tropical backwater system in India - E. V. Ramasamy; K. K. Jayasooryan; M. S. Shylesh Chandran; Mahesh Mohan (Environmental Monitoring and Assessment, 2017)

Modified Dual Winner Takes All Approach for Tri-Stereo Image Matching Using Disparity Space Images - Raghavendra Hemant Bhalerao; Shirish S. Gedam; Krishna Mohan Buddhiraju (Journal of the Indian Society of Remote Sensing, 2017)

Generation and Validation of two Day Composite Wind Fields from Oceansat-2 Scatterometer - Tata V. S. Udaya Bhaskar; Chiranjivi Jayaram; Saurabh Bansal; K Krishna Mohan; Debadatta Swain (Journal of the Indian Society of Remote Sensing, 2017)

Evaluation of the Soil Conservation Service curve number methodology using data from agricultural plots - Mohan Lal; S. K. Mishra; Ashish Pandey; R. P. Pandey; P. K. Meena; Anubhav Chaudhary; Ranjit Kumar Jha; Ajit Kumar Shreevastava; Yogendra Kumar (Hydrogeology Journal, 2017)

Facile synthesis of mosquitocidal silver nanoparticles using Mussaenda glabra leaf extract: characterisation and impact on non-target aquatic organisms - Marimuthu Govindarajan; Mohan Rajeswary; S. L. Hoti; Marcello Nicoletti; Giovanni Benelli (Natural Product Research, 2016)

Fatty‐acid biomarkers and tissue‐specific turnover: validation from a controlled feeding study in juvenile A tlantic croaker Micropogonias undulatus - S. D. Mohan; J. A. Mohan; T. L. Connelly; B. D. Walther; J. W. McClelland (Journal of Fish Biology, 2016)
Fatty‐acid ( FA ) profiles of liver and muscle tissue from juvenile Atlantic croaker Micropogonias undulatus were examined over a 15 week diet‐switch experiment to establish calibration coefficients ( CC ) and improve understanding of consumer–diet relationships for field applications. Essential FAs [docosahexaenoic acid ( DHA ), 22:6n‐3 and eicosapentaenoic acid ( EPA ) , 20:5n‐3] decreased and 18:2n‐6 increased in tissues of M. undulatus fed diets with increasing proportions of terrestrial v. marine lipid sources. Non‐linear models used to estimate the incorporation rate and days to saturation of per cent 18:2n‐6 in tissues showed that livers incorporated 18:2n‐6 faster than muscle, but the proportions of 18:2n‐6 in muscle were higher. CCs were established to determine proportions of FA deposition in tissues relative to diet. Many CCs were consistent amongst diet treatments, despite growth and dietary differences. The CCs can be used to discern FA modification and retention within tissues and as tools for future quantitative estimates of diet histories. Incorporation rates and CCs of 18:2n‐6 were applied to a sub‐set of field samples of wild M. undulatus to understand habitat use and feeding ecology. Altogether, these results suggest that FAs provide a time‐integrated measure of diet in aquatic food webs and are affected by tissue type, growth rate and the influence of mixed diets.

Comparative and evolutionary analysis of α-amylase gene across monocots and dicots - Sorabh Sethi; Johar S. Saini; Amita Mohan; Navreet K. Brar; Shabda Verma; Navraj K. Sarao; Kulvinder S. Gill (Functional & Integrative Genomics, 2016)

Predictive Temporal Data-Mining Approach for Evolving Knowledge Based Reservoir Operation Rules - S. Mohan; N. Ramsundram (Water Resources Management, 2016)

Spectrum of DNA variants for non-syndromic deafness in a large cohort from multiple continents - Denise Yan; Demet Tekin; Guney Bademci; Joseph Foster; F. Basak Cengiz; Abhiraami Kannan-Sundhari; Shengru Guo; Rahul Mittal; Bing Zou; Mhamed Grati; Rosemary I. Kabahuma; Mohan Kameswaran; et al. (Human Genetics, 2016)

Comparing seismic susceptibility models of the Himalayan terrain - S. K. Som; P. Dasarwar; Murali Mohan; J. N. Hindayar; N. Thrideep Kumar; S. N. Chowdhuri; G. S. Darmwal; Harbans Singh (Journal of Seismology, 2016)

Developing synergy regression models with space-borne ALOS PALSAR and Landsat TM sensors for retrieving tropical forest biomass - Suman Sinha; C Jeganathan; L K Sharma; M S Nathawat; Anup K Das; Shiv Mohan (Journal of Earth System Science, 2016)

Exhaled breath markers of alveolar macrophage activity in sarcoidosis - Nitin Mohan; Rabeya Akter; Katherine Bryant; Cristan Herbert; Sharron Chow; Paul S. Thomas (Inflammation Research, 2016)

Waste Load Allocation Using Machine Scheduling: Model Application - S. Mohan; K. Pavan Kumar (Environmental Processes, 2016)

Waste Load allocation Using Machine Scheduling: Model Formulation - S. Mohan; K. Pavan Kumar (Environmental Processes, 2016)

Further evidence for the genetic basis of qualitative traits and their linkage relationships in dolichos bean (Lablab purpureus L.) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2016)

Cell surface interaction of annexin A2 and galectin-3 modulates epidermal growth factor receptor signaling in Her-2 negative breast cancer cells - Praveenkumar Shetty; Anil Bargale; Basavraj R. Patil; Rajashekar Mohan; U. S. Dinesh; Jamboor K. Vishwanatha; Pramod B. Gai; Vidya S. Patil; T. S. Amsavardani (Molecular and Cellular Biochemistry, 2016)

Angiotensin-converting enzyme 2 inhibits high-mobility group box 1 and attenuates cardiac dysfunction post-myocardial ischemia - Yan Fei Qi; Juan Zhang; Lei Wang; Vinayak Shenoy; Eric Krause; S. Paul Oh; Carl J Pepine; Michael J Katovich; Mohan K Raizada (Journal of Molecular Medicine, 2016)

An overview of particulate dry deposition: measuring methods, deposition velocity and controlling factors - S. Mariraj Mohan (International Journal of Environmental Science and Technology, 2016)

Hydrodynamic behaviour and its effects on the treatment performance of panelled anaerobic baffle-cum filter reactor - R. Renuka; S. Mariraj Mohan; S. Amal Raj (International Journal of Environmental Science and Technology, 2016)

Mapping QTL for bruchid resistance in rice bean (Vigna umbellata) - Pavithravani B. Venkataramana; Rame Gowda; Prakit Somta; S. Ramesh; A. Mohan Rao; K. Bhanuprakash; Peerasak Srinives; C. Gireesh; C. K. Pramila (Euphytica, 2016)

Selection of Suitable Window Size for Speckle Reduction and Deblurring using SOFM in Polarimetric SAR Images - Sanjay Shitole; Shaunak De; Y. S. Rao; B. Krishna Mohan; Anup Das (Journal of the Indian Society of Remote Sensing, 2015)

Evaluation of the factors controlling the spatial distribution of soil piping: a case study from the southern Western Ghats, India - S. Bhagyalekshmi; Mahesh Mohan; K. Sreedharan; B. Ajaykumar (Arabian Journal of Geosciences, 2015)

Removal of heavy metal from casting sand in valve manufacturing industry through bioremediation technique - J. S. Sudarsan; K. Prasanna; P. Kishorekumar; S. B. Sanjeev Mohan; S. Nithiyanantham (Sustainable Water Resources Management, 2015)

Copper(II) Complexes with N,O-Donor Ligands and Ofloxacin Drug as Antibacterial, DNA Interacting, Cytotoxic and SOD Mimic Agent - Parag S. Karia; Pankajkumar A. Vekariya; Anshul P. Patidar; Mohan N. Patel (Indian Journal of Microbiology, 2015)

Diversity, distribution and vegetative structure of mangroves of the Andaman and Nicobar Islands, India - P. Ragavan; Alok Saxena; P. M. Mohan; K. Ravichandran; R. S. C. Jayaraj; S. Saravanan (Journal of Coastal Conservation, 2015)

Correlation of Microalbuminuria with Estimated GFR (eGFR) by Cockcroft–Gault and MDRD Formula in Type 2 Diabetics and Hypertensives - T. K. Saha; Arabinda Mohan Bhattarai; H. S. Batra; Mithu Banerjee; Pratibha Misra; Vivek Ambade (Indian Journal of Clinical Biochemistry, 2015)

Synthesis and evaluation of new salicylaldehyde-2-picolinylhydrazone Schiff base compounds of Ru(II), Rh(III) and Ir(III) as in vitro antitumor, antibacterial and fluorescence imaging agents - Narasinga Rao Palepu; S. L. Nongbri; J. Richard Premkumar; Akalesh Kumar Verma; Kaushik Bhattacharjee; S. R. Joshi; Scott Forbes; Yurij Mozharivskyj; Romita Thounaojam; K. Aguan; Mohan Rao Kollipara (JBIC Journal of Biological Inorganic Chemistry, 2015)

Glutathione reductase a unique enzyme: molecular cloning, expression and biochemical characterization from the stress adapted C4 plant, Pennisetum glaucum (L.) R. Br - V. Mohan Murali Achary; Chinreddy S. Reddy; Prachi Pandey; Tahmina Islam; Tanushri Kaul; Malireddy K. Reddy (Molecular Biology Reports, 2015)

Tributyltin Chloride (TBTCl)-Enhanced Exopolysaccharide and Siderophore Production in an Estuarine Alcaligenes faecalis Strain - Dnyanada Khanolkar; S. K. Dubey; Milind Mohan Naik (Archives of Environmental Contamination and Toxicology, 2015)

Image cytometric analysis of nuclear and chromosomal DNA contents in two cytotypes of Aloe vera (L.) Burm. f. - Bandaru V. Rao; M. Barathi; Tavva S. S. Mohan Dev; Monika Singh (The Nucleus, 2015)

Enhancement of anticipatory postural adjustments in older adults as a result of a single session of ball throwing exercise - Alexander S. Aruin; Neeta Kanekar; Yun-Ju Lee; Mohan Ganesan (Experimental Brain Research, 2015)

The CarERF genes in chickpea (Cicer arietinum L.) and the identification of CarERF116 as abiotic stress responsive transcription factor - Amit A. Deokar; Vishwajith Kondawar; Deshika Kohli; Mohammad Aslam; Pradeep K. Jain; S. Mohan Karuppayil; Rajeev K. Varshney; Ramamurthy Srinivasan (Functional & Integrative Genomics, 2015)

Histopathological findings on innate responses of white spot disease positive Penaeus monodon (Fabricius) under semi‐intensive culture - A K Sahoo; P C Thakur; K M Shankar; C V Mohan; S R Krupesha Sharma; F Corsin (Journal of Fish Diseases, 2015)

Intravenous immunoglobulin exerts reciprocal regulation of Th1/Th17 cells and regulatory T cells in Guillain–Barré syndrome patients - Mohan S. Maddur; Magalie Rabin; Pushpa Hegde; Francis Bolgert; Moneger Guy; Jean-Michel Vallat; Laurent Magy; Jagadeesh Bayry; Srini V. Kaveri (Immunologic Research, 2014)

Genetic characterization and pathogenicity assessment of Newcastle disease virus isolated from wild peacock - Sagar A. Khulape; Satish S. Gaikwad; Madhan Mohan Chellappa; Bishnu Prasad Mishra; Sohini Dey (Virus Genes, 2014)

Analysis of L-band SAR backscatter and coherence for delineation of land-use/land-cover - N. Parihar; A. Das; V.S. Rathore; M.S. Nathawat; S. Mohan (International Journal of Remote Sensing, 2014)

Experimental Verification of the Effect of Slope and Land Use on SCS Runoff Curve Number - S. K. Mishra; Anubhav Chaudhary; Raj Kaji Shrestha; Ashish Pandey; Mohan Lal (Water Resources Management, 2014)

Mercury in the sediments of Vembanad Lake, western coast of India - Mahesh Mohan; M S Shylesh Chandran; K K Jayasooryan; E V Ramasamy (Environmental Monitoring and Assessment, 2014)

Latitudinal shifts in the Polar Front in Indian sector of the Southern Ocean: evidences from silicoflagellate assemblage - Suhas S. Shetye; Rahul Mohan; Abhilash Nair (Geosciences Journal, 2014)

Purification and kinetic characterization of polygalacturonase - 3 from palmyrah palm (Borassus flabellifer L) - B. S. Sandeep; T. C. Kishor Mohan; K. Murugan (Journal of Plant Biochemistry and Biotechnology, 2014)

Genetics of growth habit and photoperiodic response to flowering time in dolichos bean (Lablab purpureus (L.) Sweet) - C. M. KEERTHI; S. RAMESH; M. BYREGOWDA; A. MOHAN RAO; B. S. RAJENDRA PRASAD; P. V. VAIJAYANTHI (Journal of Genetics, 2014)

Contrasting productivity and redox potential in Arabian Sea and Bay of Bengal - Suhas S. Shetye; Maruthadu Sudhakar; Rahul Mohan; Babula Jena (Journal of Earth Science, 2014)

The seasonal timing of warming that controls onset of the growing season - James S. Clark; Jerry Melillo; Jacqueline Mohan; Carl Salk (Global Change Biology, 2014)
Forecasting how global warming will affect onset of the growing season is essential for predicting terrestrial productivity, but suffers from conflicting evidence. We show that accurate estimates require ways to connect discrete observations of changing tree status (e.g., pre‐ vs. post budbreak) with continuous responses to fluctuating temperatures. By coherently synthesizing discrete observations with continuous responses to temperature variation, we accurately quantify how increasing temperature variation accelerates onset of growth. Application to warming experiments at two latitudes demonstrates that maximum responses to warming are concentrated in late winter, weeks ahead of the main budbreak period. Given that warming will not occur uniformly over the year, knowledge of when temperature variation has the most impact can guide prediction. Responses are large and heterogeneous, yet predictable. The approach has immediate application to forecasting effects of warming on growing season length, requiring only information that is readily available from weather stations and generated in climate models.

GSL2 over-expression confers resistance to Pectobacterium atrosepticum in potato - Sara Mohan; Sathiyamoorthy Meiyalaghan; Julie M. Latimer; Michelle L. Gatehouse; Katrina S. Monaghan; Bhanupratap R. Vanga; Andrew R. Pitman; E. Eirian Jones; Anthony J. Conner; Jeanne M. E. Jacobs (Theoretical and Applied Genetics, 2014)

Increased circulatory levels of lipopolysaccharide (LPS) and zonulin signify novel biomarkers of proinflammation in patients with type 2 diabetes - B. Jayashree; Y. S. Bibin; D. Prabhu; C. S. Shanthirani; K. Gokulakrishnan; B. S. Lakshmi; V. Mohan; M. Balasubramanyam (Molecular and Cellular Biochemistry, 2014)

Analytical solutions for transient temperature distribution in a geothermal reservoir due to cold water injection - Sayantan Ganguly; M. S. Mohan Kumar (Hydrogeology Journal, 2014)

The N-terminal region containing the zinc finger domain of tobacco streak virus coat protein is essential for the formation of virus-like particles - Chhavi Mathur; Kalyani Mohan; T. R. Usha Rani; M. Krishna Reddy; Handanahal S. Savithri (Archives of Virology, 2014)

Mapping QTL for grain yield and other agronomic traits in post-rainy sorghum [Sorghum bicolor (L.) Moench] - R. Nagaraja Reddy; R. Madhusudhana; S. Murali Mohan; D. V. N. Chakravarthi; S. P. Mehtre; N. Seetharama; J. V. Patil (Theoretical and Applied Genetics, 2013)

Radiation-induced TNFα cross signaling-dependent nuclear import of NFκB favors metastasis in neuroblastoma - Sheeja Aravindan; Mohan Natarajan; Terence S. Herman; Natarajan Aravindan (Clinical & Experimental Metastasis, 2013)

Influence of salicylic acid and methyl jasmonate elicitation on anthocyanin production in callus cultures of Rosa hybrida L. - Mohan Ram; K. V. Prasad; S. K. Singh; B. S. Hada; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Isolation and Molecular Characterisation of Alkaline Protease Producing Bacillus thuringiensis - Annapurna S. Agasthya; Naresh Sharma; Anand Mohan; Prabhpreet Mahal (Cell Biochemistry and Biophysics, 2013)

The influence of Indian Ocean sea surface temperature on the variability of monsoon rainfall over India - Lorna R. Nayagam; J. Rajesh; H. S. Ram Mohan (International Journal of Climatology, 2013)
This study focuses on the spatial and temporal variability of southwest monsoon (SWM) and northeast monsoon (NEM) rainfall over India, after the 1976–1977 regime shift. Through wavelet analysis the dominant mode of variability in the SWM and NEM rainfall is found to be in the 2–8‐year scale (ENSO band). Therefore, scale‐averaged wavelet power (SAP) of SWM (SAPSWM) and NEM (SAPNEM) rainfall obtained from a high‐resolution dataset for the period 1977–2001 was subjected to empirical orthogonal function analysis, in order to understand the homogenous regions of rainfall variability. As the study utilizes SAP, the decadal variability is observed in the spatial and temporal patterns of rainfall. The maximum variability of SAPSWM rainfall is found to be in the 2–4‐year period, whereas, for the SAPNEM rainfall, the biennial mode explains the variability over the core region of NEM rainfall. Significant power is also observed in the 4‐year period. The evolution of the principal components (PCs) is consistent with the above/below normal rainfall received over the region. Similar analysis has been carried out also for the SAP of monthly sea surface temperature (SAPSST) over Indian Ocean for the months from January to September. Compared with any other month, the decadal changes of the PCs of SAPSWM and SAPNEM rainfall are highly correlated with the decadal variations of PC1 of SAPSST for the month of March. Therefore, the relation between the rainfall and SST was explained using SAPSST for the month of March. Significant biennial power is also observed in March SST over southeast Indian Ocean (85–110°E and 5–40°S) after the climate shift of 1976. In order to identify any change in the relation between NEM rainfall and SAPSST (March) before and after 1976, a correlation between NEM rainfall and PC1 of SAPSST (March) was found for the period 1951–1975 and 1977–2001. Results show that correlation has increased after 1976. Therefore, this PC can be made use of in the prediction of NEM rainfall. Copyright © 2012 Royal Meteorological Society

Purification, characterization and kinetic properties of extracellular l-asparaginase produced by Cladosporium sp. - N. S. Mohan Kumar; H. K. Manonmani (World Journal of Microbiology and Biotechnology, 2013)

Multiple Approaches Towards Decolorization and Reuse of a Textile Dye (VB-B) by a Marine Bacterium Shewanella decolorationis - S. Satheesh Babu; C. Mohandass; A. S. Vijay Raj; R. Rajasabapathy; Mohan A. Dhale (Water, Air, & Soil Pollution, 2013)

DRE-binding transcription factor gene (LlaDREB1b) is regulated by various abiotic stresses in Lepidium latifolium L. - Sanjay Mohan Gupta; Pankaj Pandey; P. S. Negi; V. Pande; Atul Grover; Vikas Y. Patade; Zakwan Ahmed (Molecular Biology Reports, 2013)

Bamboo Shoots: A Novel Source of Nutrition and Medicine - Poonam Singhal; Lalit Mohan Bal; Santosh Satya; P. Sudhakar; S. N. Naik (Critical Reviews in Food Science and Nutrition, 2013)

Terpenoids of plant origin inhibit morphogenesis, adhesion, and biofilm formation by Candida albicans - Jayant S. Raut; Ravikumar B. Shinde; Nitin M. Chauhan; S. Mohan Karuppayil (Biofouling, 2013)

Mechanical Behaviour of Reservoir Rock Under Brine Saturation - Richa Shukla; P. G. Ranjith; S. K. Choi; A. Haque; Mohan Yellishetty; Li Hong (Rock Mechanics and Rock Engineering, 2013)

Earthworm diversity at Nilgiri biosphere reserve, Western Ghats, India - M. S. Shylesh Chandran; S. Sujatha; Mahesh Mohan; J. M. Julka; E. V. Ramasamy (Biodiversity and Conservation, 2012)

Advances in genetics and molecular breeding of three legume crops of semi-arid tropics using next-generation sequencing and high-throughput genotyping technologies - Rajeev K Varshney; Himabindu Kudapa; Manish Roorkiwal; Mahendar Thudi; Manish K Pandey; Rachit K Saxena; Siva K Chamarthi; Murali Mohan S; Nalini Mallikarjuna; Hari Upadhyaya; Pooran M Gaur; L Krishnamurthy; et al. (Journal of Biosciences, 2012)

Association mapping for pre-harvest sprouting tolerance in common wheat (Triticum aestivum L.) - V. Jaiswal; R. R. Mir; A. Mohan; H. S. Balyan; P. K. Gupta (Euphytica, 2012)

Evaporation-precipitation variability over Indian Ocean and its assessment in NCEP Climate Forecast System (CFSv2) - Samir Pokhrel; Hasibur Rahaman; Anant Parekh; Subodh Kumar Saha; Ashish Dhakate; Hemantkumar S. Chaudhari; Rakesh Mohan Gairola (Climate Dynamics, 2012)

Recent Advances of Agricultural Biotechnology in the Light of Climate Change - P. Pushpangadan; T. P. Ijinu; Vipin Mohan Dan; Alvin Thomas; S. Avinash; V. George (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Synthesis, characterization, antibacterial activity and DNA interaction studies of drug-based mixed ligand copper(II) complexes with terpyridines - Mohan N. Patel; Promise A. Dosi; Bhupesh S. Bhatt (Medicinal Chemistry Research, 2012)

Offshore depositional sequence of 2004 tsunami from Chennai, SE coast of India - M. P. Jonathan; S. Srinivasalu; N. Thangadurai; N. Rajeshwara-Rao; V. Ram-Mohan; T. Narmatha (Natural Hazards, 2012)

Design, synthesis, and biological evaluation of novel 2,4-thiazolidinedione derivatives as histone deacetylase inhibitors targeting liver cancer cell line - Rhea Mohan; Ajit K. Sharma; Sanjay Gupta; C. S. Ramaa (Medicinal Chemistry Research, 2012)

Synthesis and preliminary evaluation of difluorinated 1,3-propanediones as potential agents in the treatment of breast cancer - Tabreskhan Pathan; Sachin Ingale; Ashish Sharma; Rhea Mohan; C. S. Ramaa (Medicinal Chemistry Research, 2012)

Impact of Annular Solar Eclipse of 15 January 2010 on the Atmospheric Boundary Layer Characteristics Over Thumba: A Case Study - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar (Pure and Applied Geophysics, 2012)

Expression of medium and heavy chain neurofilaments in the developing human auditory cortex - Arvind Singh Pundir; L. Shahul Hameed; P. C. Dikshit; Praveen Kumar; Surender Mohan; Bishan Radotra; S. K. Shankar; Anita Mahadevan; Soumya Iyengar (Brain Structure and Function, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Observational study of cloud base height and its frequency over a tropical station, Thiruvananthapuram, using a ceilometer - Hamza Varikoden; R. Harikumar; R. Vishnu; V. Sasi Kumar; S. Sampath; S. Murali Das; G. Mohan Kumar (International Journal of Remote Sensing, 2011)

Wood exudates: an overview on aromatic gums and resins - K. Murugesan; G. Ravi kumar; S. H. Jain; S. Mohan; Smitha G. Nair (Journal of the Indian Academy of Wood Science, 2011)

Evaluation of wood extract of Dysoxylum malabaricum Bedd. against the plant pathogenic fungus, Fusarium oxysporum Schlecht - S. Mohan; H. C. Nagaveni; S. H. Jain; G. Ravikumar (Journal of the Indian Academy of Wood Science, 2011)

Atmospheric Surface-Layer Response to the Annular Solar Eclipse of 15 January 2010 over Thiruvananthapuram, India - D. Bala Subrahamanyam; T. J. Anurose; Mannil Mohan; M. Santosh; N. V. P. Kiran Kumar; S. Sijikumar; S. S. Prijith; Marina Aloysius (Boundary-Layer Meteorology, 2011)

Decadal frequency and trends of extreme excess/deficit rainfall during the monsoon season over different meteorological sub-divisions of India - N. Subash; H. S. Ram Mohan; A. K. Sikka (Hydrological Sciences Journal, 2011)

Trend detection in rainfall and evaluation of standardized precipitation index as a drought assessment index for rice–wheat productivity over IGR in India - N. Subash; H. S. Ram Mohan (International Journal of Climatology, 2011)
The frequency and intensity of meteorological droughts over the Indo‐Gangetic Region (IGR) of India pertaining to the rice crop during kharif season (June to July to October to November) and the wheat crop during the rabi season (November to December to March) were assessed using the standardized precipitation index (SPI). The monthly distribution of rainfall is more crucial than the cumulative seasonal rainfall on rice–wheat (RW) productivity. Consequently, an attempt was made to measure the effectiveness of using monthly SPI from June to September to assess drought on RW productivity over five major RW growing states of IGR in India. An attempt is also made to test the use of monthly SPI for the early kharif rice and rabi wheat forecasts for these states. The long‐term (1906–2005) mean annual rainfall of IGR is 1099.1 mm with a standard deviation of 115.7 mm and a coefficient of variation of 10.5%. It was observed that the kharif rice productivity index and monthly SPI from June to September have a significant ( R 2 = 0.44) multiple regression at 0.001 level over IGR. It was also observed that in the Indo‐Gangetic Region, the wheat productivity index and monthly SPI (June to September) have an insignificant ( R 2 = 0.21) multiple regression. It indicated that the monthly distribution of monsoon rainfall in terms of the SPI accounted for 44% yield variability in rice and 21% yield variability in wheat. Thus, these indices may be used for forecasting the productivity of the RW system over IGR states in India. Copyright © 2010 Royal Meteorological Society

A Simple Rationally Integrated Drought Indicator for Rice–Wheat Productivity - N. Subash; H. S. Ram Mohan (Water Resources Management, 2011)

Image cytometric determination of nuclear and chromosomal DNA contents in Allium cepa L. - V. Rao Bandaru; Tavva S. S. Mohan Dev; P. V. Arjuna Rao; M. V. Subba Rao (The Nucleus, 2011)

Impaired miR-146a expression links subclinical inflammation and insulin resistance in Type 2 diabetes - M. Balasubramanyam; S. Aravind; K. Gokulakrishnan; P. Prabu; C. Sathishkumar; H. Ranjani; V. Mohan (Molecular and Cellular Biochemistry, 2011)

Petroleum hydrocarbon concentrations in ten commercial fish species along Tamilnadu coast, Bay of Bengal, India - S. Veerasingam; R. Venkatachalapathy; P. Raja; S. Sudhakar; V. Rajeswari; R. Mohamed Asanulla; R. Mohan; P. Sutharsan (Environmental Science and Pollution Research, 2011)

Mucuna pruriens attenuates haloperidol-induced orofacial dyskinesia in rats - Amjadkhan A. Pathan; Mahalaxmi Mohan; Ameya S. Kasture; Sanjay B. Kasture (Natural Product Research, 2011)

Korean ginseng extract attenuates reserpine-induced orofacial dyskinesia and improves cognitive dysfunction in rats - Chetankumar R. Sanghavi; Shrikant A. Barhate; Manoj S. Mahajan; Mahalaxmi Mohan; Sanjay B. Kasture (Natural Product Research, 2011)

Role of dynamics in the advection of aerosols over the Arabian Sea along the west coast of peninsular India during pre-monsoon season: A case study based on satellite data and regional climate model - Marina Aloysius; S Sijikumar; S S Prijith; Mannil Mohan; K Parameswaran (Journal of Earth System Science, 2011)

Temporal changes in circulating levels of plasma interleukin-8 during peripartum period in Murrah buffaloes (Bubalus bubalis) under subtropical climate - Vijay Kumar; Parveen Kumar; Krishna Mohan; Mihir Sarkar; K. P. Suresh; M. S. Chauhan; B. S. Prakash (Tropical Animal Health and Production, 2011)

An investigation into observational characteristics of rainfall and temperature in Central Northeast India—a historical perspective 1889–2008 - N. Subash; A. K. Sikka; H. S. Ram Mohan (Theoretical and Applied Climatology, 2011)

Practices contributing to biotic pollution in Air-conditioned indoor environments - A. A. Haleem Khan; S. Mohan Karuppayil (Aerobiologia, 2011)

Induction of anthocyanin pigments in callus cultures of Rosa hybrida L. in response to sucrose and ammonical nitrogen levels - Mohan Ram; K. V. Prasad; Charanjit Kaur; S. K. Singh; Ajay Arora; Surendra Kumar (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Bacterial Diversity of Lonar Soda Lake of India - Kshipra B. Deshmukh; Anupama P. Pathak; Mohan S. Karuppayil (Indian Journal of Microbiology, 2011)

Estimating aquifer thickness using multiple pumping tests - Jean-Christophe Maréchal; Jean-Michel Vouillamoz; M. S. Mohan Kumar; Benoit Dewandel (Hydrogeology Journal, 2010)

Study on the Variations of Mineral Elements in Swertia speciosa (G. Don) - Jagmohan S. Negi; Pramod Singh; Geeta J. nee Pant; Mohan S. Maniyari Rawat (Biological Trace Element Research, 2010)

Quantification of Mineral Elements of Rheum emodi Wallr. (Polygonaceae) - Pramod Singh; Jagmohan S. Negi; Mohan S. M. Rawat; Geeta Joshi nee Pant (Biological Trace Element Research, 2010)

Chemical constituents of the essential oil from Dysoxylum malabaricum Bedd. wood of Western Ghats, India - S. Mohan; R. Ezhumalai; S. H. Jain; G. Ravikumar (Journal of the Indian Academy of Wood Science, 2010)

Complete nucleotide sequence of cherry virus A (CVA) infecting sweet cherry in India - M. S. Noorani; P. Awasthi; Rahul Mohan Singh; Raja Ram; M. P. Sharma; S. R. Singh; N. Ahmed; V. Hallan; A. A. Zaidi (Archives of Virology, 2010)

Ostracoda as an aid in identifying 2004 tsunami sediments: a report from SE coast of India - S. M. Hussain; S. P. Mohan; M. P. Jonathan (Natural Hazards, 2010)

Identification of quantitative trait loci associated with resistance to foliar diseases in sorghum [Sorghum bicolor (L.) Moench] - S. Murali Mohan; R. Madhusudhana; K. Mathur; D. V. N. Chakravarthi; Sanjay Rathore; R. Nagaraja Reddy; K. Satish; G. Srinivas; N. Sarada Mani; N. Seetharama (Euphytica, 2010)

Study of evaluation of groundwater in Gadilam basin using hydrogeochemical and isotope data - Mohan Viswanathan Prasanna; S. Chidambaram; A. Shahul Hameed; K. Srinivasamoorthy (Environmental Monitoring and Assessment, 2010)

Trace Elements Contents in Asparagus curillus (Buch.-Ham.) ex Roxb. - Jagmohan S. Negi; Pramod Singh; Geeta J. nee Pant; Mohan S. Maniyari Rawat (Biological Trace Element Research, 2010)

Evaluation of SSR Markers for the Assessment of Genetic Diversity and Fingerprinting of Gossypium hirsutum Accessions - Arunita Rakshit; S. Rakshit; V. Santhy; V. P. Gotmare; P. Mohan; V. V. Singh; S. Singh; J. Singh; H. S. Balyan; P. K. Gupta; S. R. Bhat (Journal of Plant Biochemistry and Biotechnology, 2010)

Changes in endogenous estrogens and expression of behaviors associated with estrus during the periovulatory period in Heatsynch treated Murrah buffaloes (Bubalus bubalis) - Krishna Mohan; B. S. Prakash (Tropical Animal Health and Production, 2010)

Variation of Trace Elements Contents in Asparagus racemosus (Willd) - Jagmohan S. Negi; Pramod Singh; Geeta J. Nee Pant; Mohan S. Maniyari Rawat; H. K. Pandey (Biological Trace Element Research, 2010)

Parameter Estimation in Water Distribution Networks - Shanmugam Mohan Kumar; Shankar Narasimhan; S. Murty Bhallamudi (Water Resources Management, 2010)

A study on pre- and post-tsunami shallow deposits off SE coast of India from the 2004 Indian Ocean tsunami: a geochemical approach - S. Srinivasalu; M. P. Jonathan; N. Thangadurai; V. Ram-Mohan (Natural Hazards, 2010)

Erratum to: Comparative study of experimental foot-and-mouth disease in cattle (Bos indicus) and buffaloes (Bubalus bubalis) - Mohan S. Maddur; Mukund R. Gajendragad; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2010)

Temporal changes in endogenous estrogens and expression of behaviors associated with estrus during the periovulaory period in Murrah buffaloes (Bubalus bubalis) - Krishna Mohan; Vijay Kumar; Mihir Sarkar; B. S. Prakash (Tropical Animal Health and Production, 2010)

Identification of quantitative trait loci for resistance to shoot fly in sorghum [Sorghum bicolor (L.) Moench] - K. Satish; G. Srinivas; R. Madhusudhana; P. G. Padmaja; R. Nagaraja Reddy; S. Murali Mohan; N. Seetharama (Theoretical and Applied Genetics, 2009)

Auxin-binding proteins without KDEL sequence in the moss Funaria hygrometrica - Kishore C. S. Panigrahi; Madhusmita Panigrahy; Marco Vervliet-Scheebaum; Daniel Lang; Ralf Reski; Man Mohan Johri (Plant Cell Reports, 2009)

Molecular mapping of rice blast resistance gene Pi-1(t) in the elite indica variety Samba mahsuri - M. Srinivas Prasad; B. Aruna Kanthi; S. M. Balachandran; M. Seshumadhav; K. Madhan Mohan; B. C. Viraktamath (World Journal of Microbiology and Biotechnology, 2009)

Genome-wide QTL analysis for pre-harvest sprouting tolerance in bread wheat - Amita Mohan; Pawan Kulwal; Ravinder Singh; Vinay Kumar; Reyazul Rouf Mir; Jitendra Kumar; Manoj Prasad; H. S. Balyan; P. K. Gupta (Euphytica, 2009)

Isolation, identification and testing for allergenicity of fungi from air-conditioned indoor environments - A. A. Haleem Khan; S. Mohan Karuppayil; C. Manoharachary; I. K. Kunwar; S. Waghray (Aerobiologia, 2009)

Identification of quantitative trait loci for agronomically important traits and their association with genic-microsatellite markers in sorghum - G. Srinivas; K. Satish; R. Madhusudhana; R. Nagaraja Reddy; S. Murali Mohan; N. Seetharama (Theoretical and Applied Genetics, 2009)

Comparative study of experimental foot-and-mouth disease in cattle (Bos indicus) and buffaloes (Bubalis bubalus) - Mohan S. Maddur; Mukund R. Gajendragad; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Kinetics of immune response to foot-and-mouth disease virus (type Asia 1) in experimental cattle - Mohan S. Maddur; Mukund R. Gajendragad; Subodh Kishore; Susurla Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Nitrilase-catalysed conversion of acrylonitrile by free and immobilized cells of Streptomyces sp. - V. K. Nigam; A. K. Khandelwal; R. K. Gothwal; M. K. Mohan; B. Choudhury; A. S. Vidyarthi; P. Ghosh (Journal of Biosciences, 2009)

Kinetics of immune response to foot-and-mouth disease virus (type Asia 1) in experimental cattle - M. S. Mohan; M. R. Gajendragad; Subodh Kishore; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2009)

Origin and characterisation of microparticles in an ice core from the Central Dronning Maud Land, East Antarctica - C. M. Laluraj; K. P. Krishnan; M. Thamban; R. Mohan; S. S. Naik; W. D’Souza; R. Ravindra; A. Chaturvedi (Environmental Monitoring and Assessment, 2009)

Estimation of forest biophysical variables from Indian Earth Observation Satellite Cartosat‐1 stereo data - M. M. Kimothi; S. Mohan; R. B. Singh; P. Soni; H. B. Vashistha; Ajai (International Journal of Remote Sensing, 2009)

Association of FAK activation with lentivirus-induced disruption of blood-brain barrier tight junction–associated ZO-1 protein organization - Nathan S Ivey; Nicole A Renner; Terri Moroney-Rasmussen; Mahesh Mohan; Rachel K Redmann; Peter J Didier; Xavier Alvarez; Andrew A Lackner; Andrew G. MacLean (Journal of NeuroVirology, 2009)

Development of tomato hybrids resistant to tomato leaf curl virus disease in South India - K. S. Shankarappa; Sriharsha; K. T. Rangaswamy; D. S. Aswathanarayana; H. A. Prameela; R. S. Kulkarni; V. Muniyappa; A. Mohan Rao; M. N. Maruthi (Euphytica, 2008)

Comparative study of experimental Foot-and-Mouth Disease in cattle (Bos indicus) and buffaloes (Bubalis bubalus) - M. S. Mohan; M. R. Gajendragad; S. Gopalakrishna; Nem Singh (Veterinary Research Communications, 2008)

Watershed development in India. 1. Biophysical and societal impacts - Ian Calder; Ashvin Gosain; M. S. Rama Mohan Rao; Charles Batchelor; M. Snehalatha; Emma Bishop (Environment, Development and Sustainability, 2008)

Watershed development in India. 2. New approaches for managing externalities and meeting sustainability requirements - Ian Calder; Ashvin Gosain; M. S. Rama Mohan Rao; Charles Batchelor; James Garratt; Emma Bishop (Environment, Development and Sustainability, 2008)

Development of formaldehyde-free leathers in the perspective of retanning: part II. Combination of formaldehyde-free retanning syntans - C. Ram Mohan; S. Saravanabhavan; P. Thanikaivelan; J. Raghava Rao; Balachandran Unni Nair (Clean Technologies and Environmental Policy, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Influence of circulation parameters on the AOD variations over the Bay of Bengal during ICARB - Marina Aloysius; Mannil Mohan; S. Suresh Babu; Vijayakumar S. Nair; K. Parameswaran; K. Krishna Moorthy (Journal of Earth System Science, 2008)

A novel association of a polymorphism in the first intron of adiponectin gene with type 2 diabetes, obesity and hypoadiponectinemia in Asian Indians - Karani S. Vimaleswaran; Venkatesan Radha; Kandaswamy Ramya; Hunsur Narayan Sathish Babu; Nageshappa Savitha; Venkataramaiah Roopa; Dhar Monalisa; Raj Deepa; Saurabh Ghosh; Partha P. Majumder; M. R. Sathyanarayana Rao; Viswanathan Mohan (Human Genetics, 2008)

An empirical model for the seasonal prediction of southwest monsoon rainfall over Kerala, a meteorological subdivision of India - Lorna R. Nayagam; Rajesh Janardanan; H. S. Ram Mohan (International Journal of Climatology, 2008)
There are several studies showing a skillful empirical prediction of the All India Summer Monsoon Rainfall (AISMR) based on various combination of parameters as the predictors. However, the southwest monsoon rainfall over Kerala, a meteorological subdivision of India, bears a considerably low correlation coefficient with the AISMR. This implies that the existing predictors in the long‐range forecast models of the AISMR do not have much influence on the Kerala Summer Monsoon Rainfall (KSMR). This study attempts to examine the relationship of some ocean and atmospheric parameters with the rainfall and to formulate a linear multiple regression model for the long‐range forecast over a small area like the Kerala. Parameters having significant correlation (significant at 1% level) with the KSMR were identified for the period 1961–1994. The consistency of the relationship between these parameters and the KSMR was checked by doing a 21‐year sliding window correlation (significant at 5% level). Using a stepwise regression method, seven predictors, explaining a significant amount of variance in the KSMR were selected and a linear multiple regression model was developed. The parameters that explain the high inter‐annual variability of the KSMR are specific humidity, sensible heat net flux, relative humidity, zonal wind at 70 and 10 hPa, meridional wind and geopotential height. The characteristics of the forecast and its reliability were studied by various statistical techniques such as, Durbin Watson statistics and variance inflation factor. The model has a multiple correlation of 0.943 and coefficient of determination of 88.8%. The root mean square error (RMSE) was 6.60% (15.80%), bias (BIAS) was − 0.26% (6.20%), absolute error (ABSE) was 5.33% (13.15%) of mean rainfall for the training (test) period respectively. Climatological predictions were also made and the RMSE was (17.90%), BIAS (−5.40%) and ABSE (15.16%) of mean rainfall. The selected parameters were at least 2 months prior to the monsoon season and hence have predictive value. Copyright © 2007 Royal Meteorological Society

Synergistic interaction between sublethal doses of Bacillus thuringiensis and Campoletis chlorideae in managing Helicoverpa armigera - M. Mohan; S. N. Sushil; J. C. Bhatt; G. T. Gujar; H. S. Gupta (BioControl, 2008)

Alteration of apoptotic signaling molecules as a function of time after radiation in human neuroblastoma cells - Natarajan Aravindan; Rakhesh Madhusoodhanan; Mohan Natarajan; Terence S. Herman (Molecular and Cellular Biochemistry, 2008)

Spore Shedding in Catenella impudica from the Godavari Estuary at Bhiravapalem, India - G. Mohan Narasimha Rao; G. Subba Rangaiah; S. V. V. S. N. Dora (Algae, 2008)

Lipid peroxidation and antioxidant status in patients with rheumatoid arthritis - Krishna Mohan Surapneni; V. S. Chandrasada Gopan (Indian Journal of Clinical Biochemistry, 2008)

Socio-economic and environmental implications of the hydroelectric projects in Uttarakhand Himalaya, India - Naresh Rana; S. P. Sati; Y. P. Sundriyal; Madan Mohan Doval; Navin Juyal (Journal of Mountain Science, 2007)

Effect of Therapy on Serum Zinc and Copper in Primary Complex of Children - G. Mohan; S. Kulshreshtha; R. Dayal; M. Singh; P. Sharma (Biological Trace Element Research, 2007)

Activity-directed fractionation and isolation of four antibacterial compounds from Abrus precatorius L. roots - GB Zore; V Awad; AD Thakre; UK Halde; NS Meshram; BS Surwase; S Mohan Karuppayil (Natural Product Research, 2007)

Activity-directed-fractionation and isolation of four antibacterial compounds from Abrus precatorius L., roots - G. B. Zore; V. Awad; A. D. Thakre; U. K. Halde; N. S. Meshram; B. S. Surwase; S. Mohan Karuppayil (Natural Product Research, 2007)

Cost-ineffectiveness of serum vancomycin levels - B. A. Cunha; S. S. Mohan; N. Hamid; B. P. McDermott; P. Daniels (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Status of airborne spores and pollen in a coir factory in Kerala, India - T. S. Nayar; Thripthi Krishna Mohan; P. S. Jothish (Aerobiologia, 2007)

Evaluation of daily and diurnal signals of total precipitable water (TPW) over the Indian Ocean based on TMI retrieved 3‐day composite estimates and radiosonde data - V. Sajith; Jimmy O. Adegoke; Santosh K. Raghavan; H. S. Ram Mohan; Vinod Kumar; P. N. Preenu (International Journal of Climatology, 2007)
Tropical rainfall measuring mission (TRMM) TRMM microwave imager (TMI) retrieved total precipitable water (TPW) has been shown in previous studies to be useful for characterizing energy transport and rainfall variability over water bodies. In this study, 3‐day composite TPW values during the monsoon months of June–September in 1999 and 2003 were evaluated against radiosonde derived TPW over the coastal regions of Indian Ocean. The radiosonde measurements were from coastal locations, island stations and ship‐based observations made during the 1999 Bay of Bengal Monsoon Experiment (BOBMEX). Our study is one of the first attempts to compare TMI‐derived TPW with the BOBMEX data. Root mean square (RMS) error of 8.1 mm and a bias of −0.76 mm were obtained for TMI 3‐day composite TPW data with respect to the radiosonde data over the Indian coastal regions. TMI overestimated (underestimated) radiosonde measurements under dry (wet) atmospheric conditions. Daily TMI‐derived TPW was also validated with radiosonde measurements from the BOBMEX data for the period 21 July–28 August 1999. Diurnal signals of TPW over Bay of Bengal were found to be comparable to the in situ measurements during the same period. Copyright © 2006 Royal Meteorological Society

Mutant prion protein D202N associated with familial prion disease is retained in the endoplasmic reticulum and forms ‘curly’ intracellular aggregates - Y. Gu; S. Verghese; S. Bose; M. Mohan; N. Singh (Journal of Molecular Neuroscience, 2007)

Recombinant Antigen-based Latex Agglutination Test for Rapid Serodiagnosis of Leptospirosis - S. Dey; C. Madhan Mohan; P. Ramadass; K. Nachimuthu (Veterinary Research Communications, 2007)

Bioremediation technologies for treatment of PAH-contaminated soil and strategies to enhance process efficiency - S. Venkata Mohan; Takuro Kisa; Takeru Ohkuma; Robert A. Kanaly; Yoshihisa Shimizu (Reviews in Environmental Science and Bio/Technology, 2006)

Seasonal variation of pteropods from the Western Arabian Sea sediment trap - R. Mohan; K. Verma; L. P. Mergulhao; D. K. Sinha; S. Shanvas; M. V. S. Guptha (Geo-Marine Letters, 2006)

Coccolithophores from the central Arabian Sea: Sediment trap results - Lina P. Mergulhao; Rahul Mohan; V. S. N. Murty; M. V. S. Guptha; D. K. Sinha (Journal of Earth System Science, 2006)

Chemical Composition of Atmospheric Aerosol (PM10) at a Semi-arid Urban Site: Influence of Terrestrial Sources - P. Chandra Mouli; S. Venkata Mohan; S. Jayarama Reddy (Environmental Monitoring and Assessment, 2006)

Sequence diversity of the nucleoprotein gene of iris yellow spot virus (genus Tospovirus, family Bunyaviridae) isolates from the western region of the United States - H. R. Pappu; L. J. du Toit; H. F. Schwartz; S. K. Mohan (Archives of Virology, 2006)

Book Review - S. Mohan Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Book Review - S. Mohan Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Changes in the source and transport mechanism of terrigenous input to the Indian sector of Southern Ocean during the late Quaternary and its palaeoceanographic implications - M. Thamban; S. S. Naik; R. Mohan; A. Rajakumar; N. Basavaiah; Witty D’Souza; Sarita Kerkar; M. M. Subramaniam; M. Sudhakar; P. C. Pandey (Journal of Earth System Science, 2005)

Heavy Metal Pollution Assessment in Surface Water Bodies and its Suitability for Irrigation around the Neyevli Lignite Mines and Associated Industrial Complex, Tamil Nadu, India - R. Khan; S. H. Israili; H. Ahmad; A. Mohan (Mine Water and the Environment, 2005)

Major mutation-assisted plant breeding programs supported by FAO/IAEA - S. Mohan. Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Characterization of Insect Proteinases and Their Inhibition by Finger and Little Millet Inhibitors - S Sivakumar; M Mohan; B Thayumanavan (Journal of Plant Biochemistry and Biotechnology, 2005)

Promoter Trapping in Arabidopsis Using T-DNA Insertional Mutagenesis - Radhamony Resminath; Anand Mohan Prasad; Dhiraj R. Thakare; C. Sivanandan; S. R. Bhat; Srinivasan (Journal of Plant Biochemistry and Biotechnology, 2005)

Lipopolysaccharide-mediated protection againstKlebsiella pneumoniae-induced lobar pneumonia: Intranasalvs. intramuscular route of immunization - V. Yadav; S. Sharma; K. Harjai; H. Mohan; S. Chhibber (Folia Microbiologica, 2005)

Persistent Organochlorine Pesticide Residues in Alluvial Groundwater Aquifers of Gangetic Plains, India - K. P. Singh; A. Malik; D. Mohan; S. Sinha (Bulletin of Environmental Contamination and Toxicology, 2005)

Tagging and mapping of a rice gall midge resistance gene, Gm8, and development of SCARs for use in marker-aided selection and gene pyramiding - A. Jain; R. Ariyadasa; A. Kumar; M. N. Srivastava; M. Mohan; S. Nair (Theoretical and Applied Genetics, 2004)

Adsorptive removal of reactive azo dye from an aqueous phase onto charfines and activated carbon - S. Venkata Mohan; J. Karthikeyan (Clean Technologies and Environmental Policy, 2004)

Oxidant-antioxidant status in colorectal cancer patients—Before and after treatment - Sharmila Upadhya; Subramanya Upadhya; S. Krishna Mohan; K. Vanajakshamma; Mamatha Kunder; Seema Mathias (Indian Journal of Clinical Biochemistry, 2004)

Reduced consumption of pea protein-treated flour disks by stored-product insects - P. Pretheep-Kumar; S. Mohan (Phytoparasitica, 2004)

Rubella virus P90 associates with the cytokinesis regulatory protein Citron-K kinase and the viral infection and constitutive expression of P90 protein both induce cell cycle arrest following S phase in cell culture - C. D. Atreya; S. Kulkarni; K.V. K. Mohan (Archives of Virology, 2004)

Genetic variation in germination, growth, and survivorship of red maple in response to subambient through elevated atmospheric CO 2 - Jacqueline E. Mohan; James S. Clark; William H. Schlesinger (Global Change Biology, 2004)
Genetic variation in plant response to atmospheric carbon dioxide (CO 2 ) may have influenced paleo‐vegetation dynamics and could determine how future elevated CO 2 drives plant evolution and ecosystem productivity. We established how levels of relatedness – the maternal family, population, and provenance – affect variation in the CO 2 response of a species. This 2‐year growth chamber experiment focused on the germination, growth, biomass allocation, and survivorship responses of Acer rubrum to four concentrations of CO 2 : 180, 270, 360, and 600 μL L −1 – representing Pleistocene through potential future conditions. We found that all levels of relatedness interacted with CO 2 to contribute to variation in response. Germination responses to CO 2 varied among families and populations, growth responses depended on families and regions of origin, and survivorship responses to CO 2 were particularly affected by regional identities. Differences among geographic regions accounted for 23% of the variation in biomass response to CO 2 . If seeds produced under subambient CO 2 conditions behave similarly, our results suggest that A. rubrum may have experienced strong selection on seedling survivorship at Pleistocene CO 2 levels. Further, this species may evolve in response to globally rising CO 2 so as to increase productivity above that experimentally observed today. Species responses to future atmospheric CO 2 and the accompanying biotic effects on the global carbon cycle will vary among families, populations, and provenances.

Curcumin-induced inhibition of cellular reactive oxygen species generation: Novel therapeutic implications - M. Balasubramanyam; A. Adaikala Koteswari; R. Sampath Kumar; S. Finny Monickaraj; J. Uma Maheswari; V. Mohan (Journal of Biosciences, 2003)

Induction of systemic resistance to Xanthomonas oryzae pv. oryzae by salicylic acid in Oryza sativa (L.) - R. Mohan Babu; A. Sajeena; A. Vijaya Samundeeswari; A. Sreedhar; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Journal of Plant Diseases and Protection, 2003)

Stress and aberrant phenotypes in vitro culture - Siobhan M. Joyce; Alan C. Cassells; S. Mohan Jain (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Potential predictability of the Asian summer monsoon on monthly and seasonal time scales - R. S. Ajaya Mohan; B. N. Goswami (Meteorology and Atmospheric Physics, 2003)

Toxicology and free radicals scavenging property of Tamra bhasma - N. Pattanaik; Ajita V Singh; R. S. Pandey; B. S. Singh; Mohan Kumar; S. K. Dixit; Yamini B. Tripathi (Indian Journal of Clinical Biochemistry, 2003)

Characterization of a phytotoxic glycoprotein produced byPhoma eupyrena — A pathogen on water lettuce - R. Mohan Babu; A. Sajeena; P. Vidhyasekaran; K. Seetharaman; M. S. Reddy (Phytoparasitica, 2003)

Purification and characterization of a Ca2+-dependent/calmodulin-stimulated protein kinase from moss chloronema cells - Jacinta S D’Souza; Man Mohan Johri (Journal of Biosciences, 2003)

An Overview of the Land Surface Processes Experiment (Laspex) over a Semi-Arid Region of India - K. G. Vernekar; S. Sinha; L. K. Sadani; S. Sivaramakrishnan; S. S. Parasnis; Brij Mohan; S. Dharmaraj; M. N. Patil; J. S. Pillai; B. S. Murthy; S. B. Debaje; A. Bagavathsingh (Boundary-Layer Meteorology, 2003)

Identification and mapping of an AFLP marker linked to Gm7, a gall midge resistance gene and its conversion to a SCAR marker for its utility in marker aided selection in rice - N. Sardesai; A. Kumar; K. Rajyashri; S. Nair; M. Mohan (Theoretical and Applied Genetics, 2002)

Molecular markers for yellow stem borer Scirpophaga incertulas (Walker) resistance in rice - A. Selvi; P. Shanmugasundaram; S. Mohan Kumar; J.A.J. Raja (Euphytica, 2002)

Comparison of ocean color chlorophyll algorithms for IRS-P4 OCM sensor usingin-situ data - Prakash Chauhan; M Mohan; S R Nayak; R R Navalgund (Journal of the Indian Society of Remote Sensing, 2002)

Effect of dietary vitamin C on the inflammatory response of mrigal, Cirrhinus mrigala (Hamilton), to Freund's complete adjuvant - K S Sobhana; C V Mohan; K M Shankar (Journal of Fish Diseases, 2002)

Construction of a BAC Contig for a 3 cM Biologically Significant Region of Mouse Chromosome 1 - W.K. Gu; X.M. Li; B. Edderkaoui; D.D. Strong; K.-H.W. Lau; W.G. Beamer; L.R. Donahae; S. Mohan; D.J. Baylink (Genetica, 2002)

Carbon Stock, Afforestation and Acidic Deposition: An Analysis of Inter-Relation with Reference to Arid Areas - Sanjay Kumar; R. Datta; S. Sinha; T. Kojima; S. Katoh; M. Mohan (Water, Air, & Soil Pollution, 2001)

Plant Genetics For a Better Life-Proceedings of the 18th International Congress, Beijing, China - S. Mohan Jain; B.S. Ahloowalia; G.S. Khush; Lihuang Zhu (Euphytica, 2001)

Tissue culture-derived variation in crop improvement - S. Mohan Jain (Euphytica, 2001)

Editorial - Jain S. Mohan (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Tracing mangrove carbon in suspended matter and aquatic fauna of the Gautami–Godavari Delta, Bay of Bengal (India) - F. Dehairs; R. G. Rao; P. Chandra Mohan; A.V. Raman; S. Marguillier; L. Hellings (Hydrobiologia, 2000)

Isolation of two antifungal compounds fromNeolitsea cuipala and their activity against some plant pathogenic fungi - P. Boruah; P. Deka Bhuyan; S. C. Dutta; S. Mohan; R. K. Mathur (Folia Microbiologica, 1999)

Resistance gene analogues from rice: cloning, sequencing and mapping - R. Mago; S. Nair; M. Mohan (Theoretical and Applied Genetics, 1999)

Downregulation of the urokinase-type plasminogen activator receptor through inhibition of translation by antisense oligonucleotide suppresses invasion of human glioblastoma cells - Pamarthi M. Mohan; Sajani S. Lakka; Sanjeeva Mohanam; Yoshiaki Kin; Raymond Sawaya; Anthanassios P. Kyritsis; Garth L. Nicolson; Jasti S. Rao (Clinical & Experimental Metastasis, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Isolation and FISH mapping of Yeast Artificial Chromosomes (YACs) encompassing an allele of the Gm2 gene for gall midge resistance in rice - K. R. Rajyashri; S. Nair; N. Ohmido; K. Fukui; N. Kurata; T. Sasaki; M. Mohan (Theoretical and Applied Genetics, 1998)

Genome analysis for nucleotide interactions in fully sequenced genomes of selective prokaryotes - B. V. L. S. Prasaot; Mohan C. Vemuri (Journal of Biosciences, 1998)

Effect of short term vitamin E supplementation on lipid peroxidation in acute myocardial infarction - A. P. Jain; A. Mohan; O. P. Gupta; U. N. Jajoo; S. P. Kalantri; L. M. Srivastava (Indian Journal of Clinical Biochemistry, 1998)

Micropropagation of selected somaclones ofBegonia andSaintpaulia - S. Mohan Jain (Journal of Biosciences, 1997)

Molecular mapping of a resistance-specific PCR-based marker linked to a gall midge resistance gene (Gm4t) in rice - M. Mohan; P. V. Sathyanarayanan; A. Kumar; M. N. Srivastava; S. Nair (Theoretical and Applied Genetics, 1997)

Development and Field Performance of a Sporeless Mutant of Bacillus thuringiensis Subsp. kurstaki - K. S. Mohan; R. Asokan; C. Gopalakrishnan (Journal of Plant Biochemistry and Biotechnology, 1997)

Diversity, structure and standing stock of wood in the homegardens of Kerala in peninsular India - B. Mohan Kumar; Suman Jacob George; S. Chinnamani (Agroforestry Systems, 1994)

Infection of aerial parts of potato plants byColletotrichum cocodes and its effects on premature vine death and yield - S. K. Mohan; J. R. Davis; L. H. Sorensen; A. T. Schneider (American Journal of Potato Research, 1993)

Infection of aerial parts of potato plants byColletotrichum coccodes and its effects on premature vine death and yield - S. K. Mohan; J. R. Davis; L. H. Sorensen; A. T. Schneider (American Journal of Potato Research, 1992)

Characterization of viral proteins ofOryctes baculovirus and comparison between two geographical isolates - K. S. Mohan; K. P. Gopinathan (Archives of Virology, 1989)

Productivity, soil fertility and soil erosion under cassava based agroforestry systems - S. P. Ghosh; B. Mohan Kumar; S. Kabeerathumma; G. M. Nair (Agroforestry Systems, 1989)

Wild mouse retrovirus-induced neurogenic paralysis in laboratory mice - B. K. Pal; S. Mohan; Rosemarie Nimo; M. B. Gardner (Archives of Virology, 1983)

Oxidation of tricarboxylic acid cycle intermediates byStreptomyces nitrificans - Albert Schatz; R. Ram Mohan; Gilbert S. Trelawny (Antonie van Leeuwenhoek, 1955)